Highly purified tin-containing perovskite semiconductor material
A tin-containing perovskite layer with controlled Sn 4+ concentration and oxidation resistance addresses environmental concerns and efficiency issues in lead-based cells, enhancing solar cell performance by stabilizing the carrier lifetime and improving optical conversion efficiency.
Patent Information
- Application Number
- JP2022507201
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-09
- Filing Date
- 2021-03-09
- Publication Date
- 2025-01-29
- Estimated Expiration
- 2041-03-09
AI Technical Summary
Lead-based perovskite solar cells face environmental concerns due to lead content and issues with oxidation leading to increased hole density and reduced carrier lifetime, affecting optical conversion efficiency.
A tin-containing perovskite layer with controlled tin concentration and oxidation resistance is developed, maintaining a specific ratio of Sn 4+ to total tin atoms within a specified depth range, achieved through etching and using reducing agents to stabilize the layer.
The solution provides a perovskite layer with enhanced photovoltaic conversion efficiency and reduced oxidation, extending carrier lifetime and improving overall solar cell performance.
Smart Images

Figure 0007623714000020 
Figure 0007623714000021 
Figure 0007623714000022
Abstract
Description
[Technical field]
[0001] The present invention relates to a tin-containing perovskite semiconductor material having excellent photoelectric conversion efficiency. [Background technology]
[0002] So far, lead (Pb 2+ Solar cells that use perovskite containing lead (Sn) at the B site and exhibit high photoelectric conversion efficiencies (PCEs) of over 20% have been reported. However, there are concerns about the environmental impact of lead in solar cells that use lead-based perovskite in the light absorption layer. Therefore, from the perspective of practical application, there are plans to replace part or all of the lead with tin (Sn 2+ Solar cells that use tin-containing perovskite in which tin is replaced with tin (ZnO) in the light absorption layer are expected to be environmentally friendly solar cells (Non-Patent Document 1).
[0003] However, tin-containing perovskite is different from lead-based perovskite Pb 2+ Unlike the Sn in the material, 2+ Sn 4+ The problem is that tin-containing perovskite solar cells are easily oxidized to tin, which increases the hole density in the film and reduces the solar cell characteristics. In addition, the photoelectric conversion efficiency of tin-containing perovskite solar cells has a problem in that the lifetime of carriers generated by photoexcitation is short. [Prior art documents] [Non-patent literature]
[0004] [Non-Patent Document 1] Shi, Z.; Guo, J.; Chen, Y.; Li, Q.; Pan, Y.; Zhang, H.; Xia, Y.; Huang, W. Adv. Mater. 2017, 29, 1605005. Summary of the Invention [Problem to be solved by the invention]
[0005] In one embodiment of the invention described in this specification, the presence of trace amounts of Sn in the system 4+ By removing (capturing) Sn 2+ Sn 4+ One of the objects of the present invention is to provide a tin-containing perovskite layer which is resistant to oxidation to tin and has good photoelectric conversion efficiency.
[0006] An object of some embodiments of the invention described in this specification is to provide a luminescent material or a photoelectric conversion element (eg, an organic EL element, a solar cell) having an excellent tin-containing perovskite layer.
[0007] The invention described in this specification is not limited to the above-mentioned objectives, and may have the objective of achieving the various effects described in this specification. [Means for solving the problem]
[0008] One embodiment of the invention described in this specification is a perovskite layer containing Sn + 4 This is based on the finding from the examples that the photoelectric conversion efficiency of the tin-containing perovskite layer can be increased by setting the concentration of tin within a predetermined range.
[0009] An invention described in this specification relates to a tin-containing perovskite layer. The tin-containing perovskite layer means a perovskite layer containing tin. The perovskite layer containing tin is also called a tin-containing perovskite layer. This perovskite layer has a tin content of Sn, which is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and the atomic content of divalent tin in a second measurement region, which is a region at a depth of 40 nm from the center of the surface of the tin-containing perovskite layer. +4 40nm The value is 0% or more and 0.5% or less. +4 40nm It is preferable that the value is 0.0% or more and 0.3% or less.
[0010] Sn is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin at the center of the surface of the tin-containing perovskite layer. +4 表面 value and Sn +4 40nm It is preferable that the ratio of this value is 3 or more.
[0011] Sn is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin in the first measurement area, which is a region 20 nm deep from the center of the surface of the tin-containing perovskite layer. +4 20nm In this example, the Sn value is preferably 0.1% or more and 5% or less. +4 20nm A value of 0.1% or more and 2% or less is preferred.
[0012] Sn is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin at the center of the surface of the tin-containing perovskite layer. +4 表面 value and Sn +4 20nm It is preferable that the ratio of this value is 3 or more and 20 or less.
[0013] The atomic content of lead atoms relative to the content of tin atoms is preferably 0% or more and 900% or less.
[0014] Sn is the atomic content of tin. +4 20nm The value is between 0.1% and 5%.
[0015] The tin-containing perovskite layer means a perovskite layer containing tin. The perovskite layer is usually rectangular. Therefore, the central part of the surface of the tin-containing perovskite layer means, for example, the vicinity of the center of gravity of the surface.
[0016] The first measurement region, which is a region 20 nm deep in the center of the surface, refers to the center of the surface of the perovskite layer that is exposed by etching the surface of the perovskite layer to remove 20 nm, as described below. Etching may be performed in an oxygen-free atmosphere (e.g., in a vacuum). An example of etching is argon etching.
[0017] Sn +4 20nm The value is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin in the first measurement region. The atomic content of tetravalent tin and the atomic content of divalent tin can be obtained by separating peaks corresponding to divalent tin and tetravalent tin from the spectrum obtained by X-ray photoelectron spectroscopy (XPS) measurement and calculating the area. In addition, Gaussian fitting may be performed for peak separation, and the area may be calculated automatically using known software or programs. In other words, Sn +4 20nm The value is calculated using the following formula: Sn +4 20nm Value = 100 x (atomic content of tetravalent tin) / ((atomic content of divalent tin) + (atomic content of tetravalent tin))
[0018] As demonstrated by the examples described below, Sn +4 20nm If the value is 0.1% or more and 5% or less, the proportion of tetravalent tin decreases, and the photoelectric conversion efficiency is significantly increased while maintaining various physical properties.
[0019] Sn +4 40nm The value is the percentage of the atomic content of tetravalent tin in the sum of the atomic content of tetravalent tin and the atomic content of divalent tin in the second measurement region, which is a region 40 nm deep from the center of the surface of the tin-containing perovskite layer. The second measurement region, which is a region at a depth of 40 nm in the center of the surface, refers to the center of the surface of the perovskite layer that is exposed when the surface of the perovskite layer is etched away by 40 nm. Sn+4 40nm The value is Sn +4 20nm The value can be calculated in the same manner.
[0020] Sn +4 表面 The value is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin at the center of the surface of the tin-containing perovskite layer. +4 表面 value and Sn +4 20nm The ratio of the value to Sn +4 表面 Value / Sn +4 20 nm It can be calculated by the value.
[0021] A preferred example of the above-mentioned tin-containing perovskite layer is one that contains 0.01 ppm or more and 1000 ppm or less in total of one or more compounds selected from zero-valent tin, pyrazine-based compounds, silicon-based compounds, and germanium-based compounds.
[0022] A preferred example of the use of the above-mentioned tin-containing perovskite layer is a luminescent material having any of the above-mentioned tin-containing perovskite layers.
[0023] A preferred example of the use of the above-mentioned tin-containing perovskite layer is a display device having any of the above-mentioned tin-containing perovskite layers.
[0024] A preferred example of the use of the above-mentioned tin-containing perovskite layer is a photoelectric conversion element having any of the above-mentioned tin-containing perovskite layers.
[0025] A preferred example of the use of the above-mentioned tin-containing perovskite layer is a solar cell having any of the above-mentioned tin-containing perovskite layers. Effect of the Invention
[0026] According to this specification, the trace amount of Sn present in the system4+ By removing (capturing) Sn 2+ Sn 4+ It is possible to provide a tin-containing perovskite layer that is difficult to be oxidized to tin and has good photoelectric conversion efficiency. [Brief description of the drawings]
[0027] [Figure 1] Figure 1 is a graph instead of a drawing showing the PL spectrum when reducing agent 1 in Example 1 was used, and a summary of the results. The vertical axis of Figure 1 is intensity (arbitrary unit), and the horizontal axis is wavelength (nm). [Diagram 2] Figure 2 is a graph instead of a drawing showing the measurement results of the fluorescence lifetime when the reducing agent 1 in Example 1 was used, and a summary of the results. The vertical axis of Figure 2 is intensity (arbitrary unit), and the horizontal axis is time (n seconds). [Diagram 3] 3 is a graph instead of a drawing showing the PL spectrum when reducing agent 2 in Example 1 was used, and a summary of the results. The vertical axis of Fig. 3 is intensity (arbitrary unit), and the horizontal axis is wavelength (nm). [Figure 4] 4 is a graph instead of a drawing showing the measurement results of the fluorescence lifetime when reducing agent 2 in Example 1 was used, and a summary of the results. The vertical axis of Fig. 4 is intensity (arbitrary unit), and the horizontal axis is time (n seconds). [Diagram 5] Fig. 5 is a surface SEM photograph of a perovskite film in place of a drawing in Example 2. From the left, it shows a case where reducing agent 1 was added at 0.1 mol% relative to SnI2 (1.0 mol% relative to SnF2), a case where reducing agent 1 was added at 5.0 mol% relative to SnI2 (50 mol% relative to SnF2), a case where reducing agent 1 was added at 1 mol% relative to SnI2 (10 mol% relative to SnF2), and a case where reducing agent 1 was added at 5 mol% relative to SnI2 (50 mol% relative to SnF2). [Figure 6] 6 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 2. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Figure 7] Fig. 7 is a surface SEM photograph of a perovskite film in place of a drawing in Example 3. From the left, it shows a case where reducing agent 2 was added at 0.5 mol% relative to SnI2 (5 mol% relative to SnF2), a case where reducing agent 2 was added at 1 mol% relative to SnI2 (10 mol% relative to SnF2), a case where reducing agent 2 was added at 5 mol% relative to SnI2 (50 mol% relative to SnF2), and a case where reducing agent 2 was added at 10 mol% relative to SnI2 (100 mol% relative to SnF2). [Figure 8] 8 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 3. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Figure 9] 9 is a graph, instead of a drawing, showing the evaluation results of the solar cell characteristics in Example 4. The vertical axis shows the count, and the horizontal axis shows the current density. [Figure 10] 10 is a graph, instead of a drawing, showing the evaluation results of the solar cell characteristics in Example 4. The vertical axis shows the count, and the horizontal axis shows the voltage. [Figure 11] 11 is a graph, instead of a drawing, showing the evaluation results of the solar cell characteristics in Example 4. The vertical axis shows the count, and the horizontal axis shows the FF (fill factor). [Figure 12] 12 is a graph, instead of a drawing, showing the evaluation results of the solar cell characteristics in Example 4. The vertical axis shows the count, and the horizontal axis shows PCE (conversion efficiency). [Figure 13] 13 is a surface SEM photograph of a perovskite film in place of a drawing in Example 5. From the left, the photographs show one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 0.9 M tin-containing perovskite precursor solution, one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.2 M tin-containing perovskite precursor solution, one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.3 M tin-containing perovskite precursor solution, and one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.4 M tin-containing perovskite precursor solution. [Figure 14]14 is an SEM photograph of a cross section of a perovskite film in place of a drawing in Example 5. From the left, the photographs show one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 0.9 M tin-containing perovskite precursor solution, one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.2 M tin-containing perovskite precursor solution, one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.3 M tin-containing perovskite precursor solution, and one made from a solution in which reducing agent 2 was added at 1 mol% relative to SnI2 to a 1.4 M tin-containing perovskite precursor solution. [Figure 15] 15 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 5. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Figure 16-1] FIG. 16-1 is a photograph in lieu of a drawing showing the state before and after the addition of reducing agent 2 in Example 6. The upper left photograph is a photograph of solution (2) before the addition of reducing agent 2, and the lower left photograph is a photograph of solution (2) after the addition of reducing agent 2. The upper center photograph is a photograph of solution (3) before the addition of reducing agent 2, and the lower center photograph is a photograph of solution (3) after the addition of reducing agent 2. The upper right photograph is a photograph of solution (4) before the addition of reducing agent 2, and the lower right photograph is a photograph of solution (4) after the addition of reducing agent 2. [Figure 16-2] Figure 16-2 is a surface SEM photograph of a perovskite film in place of a drawing in Example 6. From the left, entry 1 (reference) not containing reducing agent 2, entry 2 (a DMSO solution of SnI2 to which reducing agent 2 has been added), entry 3 (a DMSO solution of SnF2 to which reducing agent 2 has been added), and entry 4 (a DMSO solution of FA0.75MA0.25SnI3 to which reducing agent 2 has been added) are shown. [Figure 17] Fig. 17 is a graph instead of a drawing showing the PL spectrum when reducing agent 2 was used in Example 6, and a summary of the results. The vertical axis of Fig. 17 is intensity (arbitrary unit), and the horizontal axis is wavelength (nm). [Figure 18]Fig. 18 is a graph instead of a drawing showing the measurement results of the fluorescence lifetime when reducing agent 2 in Example 6 was used, and a summary of the results. The vertical axis of Fig. 18 is intensity (arbitrary unit), and the horizontal axis is time (n seconds). [Figure 19] 19 is a surface SEM photograph of a perovskite film in place of a drawing in Example 6. From the left, entry 1 (reference) not containing reducing agent 2, entry 2 (a DMSO solution of SnI2 to which reducing agent 2 has been added), and entry 4 (a DMSO solution of FA0.75MA0.25SnI3 to which reducing agent 2 has been added) are shown. [Figure 20] 20 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 6. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Figure 21] Fig. 21 is a graph instead of a drawing showing the PL spectrum when reducing agent 2 in Example 7 was used, and a summary of the results. The vertical axis of Fig. 21 is intensity (arbitrary unit), and the horizontal axis is wavelength (nm). [Figure 22] Fig. 22 is a graph instead of a drawing showing the measurement results of the fluorescence lifetime when reducing agent 2 in Example 7 was used, and a summary of the results. The vertical axis of Fig. 22 is intensity (arbitrary unit), and the horizontal axis is time (n seconds). [Diagram 23] 23 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 8. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Figure 24] 24 is a graph, instead of a drawing, showing the IPCE spectrum in Example 8. The vertical axis indicates IPCE, and the horizontal axis indicates wavelength (nm). [Diagram 25] 25 is a graph instead of a drawing showing the chemical shift of SnI2 in Example 9. The upper figure shows that of Sample 1 (without adding reducing agent 2), and the lower figure shows that of Sample 2 (with adding reducing agent 2). [Figure 26]26 is a graph instead of a drawing showing the chemical shift of SnF2 in Example 9. The upper figure shows that of Sample 1 (without adding reducing agent 2), and the lower figure shows that of Sample 2 (with adding reducing agent 2). [Figure 27] FIG. 27 is a TEM photograph, in place of a drawing, showing that particles were obtained in Example 9. [Figure 28] 28 is a graph instead of a drawing showing the chemical shift of SnI4 in Example 9. The upper figure shows that of Sample 1 (without adding reducing agent 2), and the lower figure shows that of Sample 2 (with adding reducing agent 2). [Figure 29] 29 is a graph instead of a drawing showing the chemical shift of a system containing SnI4 and SnF2 in Example 9. The upper figure shows that of Sample 1 (without adding reducing agent 2), and the lower figure shows that of Sample 2 (with adding reducing agent 2). [Diagram 30] Figure 30 is a graph instead of a drawing showing the measurement results of the fluorescence lifetime when Et3SiH was used as the reducing agent in Example 10, and a summary of the results. The vertical axis of Figure 30 is intensity (arbitrary unit), and the horizontal axis is time (n seconds). [Diagram 31] 31 is a surface SEM photograph of a perovskite film in place of a drawing in Example 10. From the left, a reference containing no reducing agent, a sample in which the reducing agent Et3SiH was added at 1 mol% relative to SnI2, a sample in which the reducing agent Et3SiH was added at 5 mol%, and a sample in which the reducing agent Et3SiH was added at 10 mol% relative to SnI2 are shown. [Diagram 32] 32 is a graph, instead of a drawing, showing the solar cell characteristics (JV curve) in Example 10. The vertical axis indicates the current density, and the horizontal axis indicates the voltage. [Diagram 33] Figure 33 is a photograph in lieu of a drawing showing the state of scavenger treatment. Figure 33 shows photographs of the precursor solution before (left), immediately after (middle), and after 15 minutes of stirring (right) of the reducing agent TM-DHP. [Diagram 34]Figure 34 shows SEM images in place of drawings showing (a) the surface and (b) the cross section of a tin-containing perovskite thin film. [Diagram 35] Figure 35 shows a diagram for quantitatively evaluating tin ions contained in a perovskite thin film. Figure 35(a) shows a cross-sectional SEM image in place of a drawing, and Figure 35(b) shows the Sn 3d5 / 2 XPS spectrum of a tin-containing perovskite thin film. [Diagram 36] Figure 36 is a graph instead of a drawing showing the results of measuring the optical properties of a tin-containing perovskite thin film. Figure 36(a) shows the fluorescence spectrum. The vertical axis of Figure 36(a) shows the fluorescence intensity, and the horizontal axis shows the energy (eV). Figure 36(b) is a graph (time-resolved decay curve) instead of a drawing showing the results of measuring the fluorescence lifetime. The vertical axis of Figure 36(b) shows the fluorescence intensity (after normalization), and the horizontal axis shows the time (n seconds). [Figure 37] Figure 37 is a diagram related to elucidation of the mechanism by scavengers. Figure 37(a) is a graph instead of a diagram showing the results of NMR measurement indicating the presence of divalent tin and tetravalent tin in a DMSO-d6 solution of SnF2 before (upper row) and after (lower row) the addition of TM-DHP. Figure 37(b) is a graph instead of a diagram showing the results of NMR measurement indicating the presence of divalent tin and tetravalent tin in a DMSO-d6 solution of SnI2 before (upper row) and after (lower row) the addition of TM-DHP. Figure 37(c) is a graph instead of a diagram showing the results of NMR measurement indicating the presence of divalent tin and tetravalent tin in a DMSO-d6 solution of SnBr2 before (upper row) and after (lower row) the addition of TM-DHP. Figure 37(d) is a graph in lieu of a drawing showing the results of NMR measurements indicating the presence of divalent tin and tetravalent tin in a DMSO-d6 solution of SnCl2 before (top) and after (bottom) the addition of TM-DHP. Figure 37(e) is a photograph in lieu of a drawing showing a DMSO-d6 solution of SnF2 before (left) and after (right) the addition of TM-DHP. Figure 37(f) is a TEM photograph in lieu of a drawing showing Sn0 nanoparticles formed after the addition of TM-DHP (right). [Figure 38]Figure 38 is a graph instead of a drawing showing the characteristics of a perovskite solar cell. Figure 38(a) shows a current density-voltage curve, and Figure 38(b) shows the distribution of photoelectric conversion efficiency (PCE) of 40 cells. [Figure 39] Figure 39 shows the physical properties of the surface-treated perovskite layer. Figure 39(a) is a graph replacing a drawing showing the current density-voltage curve of a tin-containing perovskite solar cell. Figure 39(b) is a diagram showing an energy level diagram. Figure 39(c) is a graph replacing a drawing showing the external quantum efficiency (EQE) and internal quantum efficiency (IQE). Figure 39(d) is a graph replacing a drawing showing the distribution of photoelectric conversion efficiency (PCE) of 30 cells. [Diagram 40] Figure 40 is a graph in lieu of a drawing relating to a MASnI1.5Br1.5 perovskite thin film. Figure 40(a) shows the fluorescence spectrum. The vertical axis of Figure 40(a) shows the fluorescence intensity, and the horizontal axis shows the energy (eV). Figure 40(b) is a graph in lieu of a drawing showing the measurement results of the fluorescence lifetime (time-resolved decay curve). The vertical axis of Figure 40(b) shows the fluorescence intensity (after normalization), and the horizontal axis shows the time (n seconds). [Diagram 41] Figure 41 is a graph in lieu of a drawing relating to a MASnBr3 perovskite thin film. Figure 41(a) shows the fluorescence spectrum. The vertical axis of Figure 41(a) shows the fluorescence intensity, and the horizontal axis shows the energy (eV). Figure 41(b) is a graph in lieu of a drawing showing the measurement results of the fluorescence lifetime (time-resolved decay curve). The vertical axis of Figure 41(b) shows the fluorescence intensity (after normalization), and the horizontal axis shows the time (n seconds). [Diagram 42] FIG. 42 is a graph, instead of a drawing, showing the Sn 3d5 / 2 XPS spectrum of a MASnI1.5Br1.5 perovskite thin film. [Diagram 43] Figure 43 is a graph instead of a drawing for an ASnI3-XBrX-based perovskite solar cell element fabricated using the scavenger method. Figure 43(a) shows the current density-voltage curve, and Figure 43(b) shows the external quantum efficiency (EQE). [Diagram 44]Figure 44 is a graph instead of a drawing relating to a Cs0.1FA0.6MA0.3Pb0.5Sn0.5I3 perovskite thin film. Figure 44(a) shows the fluorescence spectrum. The vertical axis of Figure 44(a) shows the fluorescence intensity, and the horizontal axis shows the energy (eV). Figure 44(b) is a graph instead of a drawing showing the measurement results of the fluorescence lifetime (time-resolved decay curve). The vertical axis of Figure 44(b) shows the fluorescence intensity (after normalization), and the horizontal axis shows the time (n seconds). [Diagram 45] Figure 45 is a graph instead of a drawing showing the current density-voltage curve of a solar cell element using a Cs0.1FA0.6MA0.3Pb0.5Sn0.5I3 perovskite film. Figure 45(a) shows the case where the scavenger method is not used, and Figure 45(b) shows the case where the scavenger method is used. [Diagram 46] FIG. 46 is a graph, instead of a drawing, showing the XPS spectrum for Sn 3d of a Cs0.1FA0.6MA0.3Pb0.5Sn0.5I3 perovskite thin film. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] Hereinafter, the embodiments for carrying out the present invention will be described with reference to the drawings. The present invention is not limited to the embodiments described below, and includes appropriate modifications of the embodiments described below within the scope obvious to those skilled in the art.
[0029] 1. Manufacturing method of perovskite layer The method for producing a tin-containing perovskite layer described herein includes the steps of adding a reducing agent to a solution containing a tin heavy halide to obtain a tin-containing perovskite precursor solution. This method for producing a perovskite layer can appropriately adopt known steps and conditions for producing a perovskite layer. For example, the method may include the steps of applying a solution containing a tin-containing perovskite compound to a substrate, applying a poor solvent to the substrate, and annealing the substrate.
[0030] Reducing Agent The reducing agent is, for example, a reducing agent that reduces tin fluoride in a tin-containing perovskite precursor solution to tin (zero-valent tin) and does not reduce tin heavy halides in the tin-containing perovskite precursor solution to tin. Reducing tin fluoride in a tin-containing perovskite precursor solution to tin does not necessarily mean completely reducing tin fluoride or ions derived from tin fluoride in the solution. It is sufficient to reduce, for example, 1% or more, 3% or more, 5% or more, or 10% or more of tin fluoride in the solution. Similarly, the term "not reducing tin heavy halides to tin" means that it is sufficient to not reduce, for example, 50% or more, 60% or more, 70% or more, 80% or more, 85% or more, 90% or more, 95% or more, or 98% or more of tin heavy halides to tin.
[0031] The redox potential of the reducing agent was measured by cyclic voltammetry, with the oxidation potential being -1.0 V vs Fc / Fc. + Above +0.8 V vs Fc / Fc + less than or equal to -0.5 V vs Fc / Fc + Above +0.3 V vs Fc / Fc + The reducing agent may also be a reducing agent having a silyl group. For example, a reducing agent having a silyl group as a basic skeleton or as a part of the basic skeleton is SnF 2 The fluorine atom of the silyl group reacts selectively with the Si atom of the silyl group, so for example, SnI 2 Compared to SnF 2 Among the reducing agents having a silyl group, Et 3 SiH is effective in extending the fluorescence lifetime, and in this case, SnF 2 It is thought that H- (hydride) generated by coordination with Si reduces Sn.)
[0032] Examples of the reducing agent are any of the compounds represented by the following formulas (I) to (V). [ka]
[0033] In formula (I), R 1~R 4 may be the same or different and are a hydrogen atom or C 1 ~C 4 R represents an alkyl group. 5 ~R 10 may be the same or different and are a hydrogen atom or C 1 ~C 4 represents an alkyl group, X 1 and X 2 may be the same or different and represent N or carbon atom. In formula (I), R 1 ~R 4 may be the same or different and are a hydrogen atom, a methyl group, or an ethyl group; R 5 ~R 10 may be the same or different and are preferably a methyl group or an ethyl group.
[0034] Among the compounds represented by formula (I), X 1 and X 2 The compound represented by N is the following compound (Ia).
[0035] [ka]
[0036] In formula (Ia), R 1 ~R 4 may be the same or different and are a hydrogen atom, a methyl group, or an ethyl group; R 5 ~R 10 may be the same or different and are preferably a methyl group or an ethyl group. For example, R 1 ~R 4 may all be hydrogen atoms or methyl groups, R 1 and R 4 is a hydrogen atom, and R 2 and R 3 may be a methyl group. R 5 ~R 10 may all be methyl groups.
[0037] Among the compounds represented by formula (I), X 1 is indicated by N and X 2 is a carbon atom is the following compound (Ib).
[0038] [ka]
[0039] In formula (Ib), R 1 ~R 4 may be the same or different and are a hydrogen atom, a methyl group, or an ethyl group; R 5 ~R 10 may be the same or different and are preferably a methyl group or an ethyl group. For example, R 1 ~R 4 may all be hydrogen atoms or methyl groups, R 1 and R 4 is a hydrogen atom, and R 2 and R 3 may be a methyl group, or R 1 is a methyl group, and R 2 ~R 4 may be a hydrogen atom. R 5 ~R 10 may all be methyl groups. A specific compound of formula (Ib) is 1 ~R 4 are all hydrogen atoms, and R 5 ~R 10 is a compound in which all the groups are methyl.
[0040] Among the compounds represented by formula (I), X 1 and X 2 is a carbon atom is the following compound (Ic).
[0041] [ka]
[0042] In formula (Ic), R 1 ~R 4 may be the same or different and are a hydrogen atom, a methyl group, or an ethyl group; R 5 ~R 10 may be the same or different and are preferably a methyl group or an ethyl group. For example, R 1 ~R 4 may all be hydrogen atoms or methyl groups, R 1 and R 4 is a hydrogen atom, and R 2 and R 3 may be a methyl group, or R 1 is a methyl group, and R 2 ~R 4 may be a hydrogen atom. 5 ~R 10 may all be methyl groups. A specific compound represented by formula (Ic) is 1 is a methyl group, and R 2 ~R 4 is a hydrogen atom, and R 5 ~R 10 is a compound in which all the groups are methyl.
[0043] [ka]
[0044] In formula (II), R 11 ~R 18 may be the same or different and are a hydrogen atom or C 1 ~C 4 R represents an alkyl group. 19 ~R 24 may be the same or different and are a hydrogen atom or C 1 ~C 4 represents an alkyl group, X 3 and X 4 may be the same or different and represent N or a single bond. In formula (II), R 11 ~R 18may be the same or different and represent a hydrogen atom, a methyl group, or an ethyl group; R 19 ~R 24 may be the same or different and represent a hydrogen atom, a methyl group, or an ethyl group; X 3 and X 4 may be the same or different and preferably represent N or a carbon atom.
[0045] Among the compounds represented by formula (II), X 3 and X 4 The compound represented by N is represented by the following formula (IIa).
[0046] [ka]
[0047] A specific compound of formula (IIa) is R 11 ~R 18 is a hydrogen atom, and R 19 ~R 24 is a compound containing a methyl group.
[0048] [ka]
[0049] In formula (III), R 31 ~R 34 may be the same or different, and are a hydrogen atom, C 1 ~C 4 Alkyl group, C 2 ~C 4 Alkenyl group, C 2 ~C 4 Alkynyl group, C 1 ~C 4 Alkoxy group, C 1 ~C 4 It represents an alkylthio group, an aryl group, an aryloxy group, or an arylthio group.
[0050] In the above, the aryl group is, for example, an aryl group having 6 to 12 carbon atoms, and examples of the aryl group are a benzyl group or a phenyl group, and the aryloxy group is, for example, an aryloxy group having 6 to 2 carbon atoms, and an example of the aryloxy group is a phenoxy group. The arylthio group is, for example, an arylthio group having 6 to 12 carbon atoms. 2 ~C 4 The alkenyl group is an alkenyl group having a straight or branched side chain with 2 to 4 carbon atoms. 2 ~C 4 Examples of alkenyl groups include vinyl, propenyl, and butenyl groups. 2 ~C 4 The alkynyl group is an alkynyl group having a straight or branched side chain with 2 to 4 carbon atoms. 2 ~C 4 Examples of alkynyl groups are ethynyl and propynyl groups. The same applies below.
[0051] In formula (III), R 31 ~R 34 may all be other than hydrogen atoms (e.g., methyl or ethyl groups), R 31 ~R 34 One of them is a hydrogen atom and the other is C 1 ~C 4 Alkyl group, C 1 ~C 4 Alkoxy group, C 1 ~C 4 It may be an alkylthio group, an aryl group, an aryloxy group, or an arylthio group.
[0052] In formula (III), R 31 is a hydrogen atom, and R 32 ~R 34 Compounds where is an ethyl group are Et 3 It is SiH.
[0053] [ka]
[0054] In formula (IV), R 35 ~R 37 may be the same or different, and are a hydrogen atom, C 1 ~C 4 Alkyl group, C 2 ~C 4 Alkenyl group, C 2 ~C 4 Alkynyl group, C 1 ~C 4 Alkoxy group, C 1 ~C 4 An alkylthio group, an aryl group, an aryloxy group, or an arylthio group. X 5 indicates a halogen atom. In formula (IV), R 35 ~R 37 may all be other than hydrogen atoms (e.g., methyl or ethyl groups). Examples of halogen atoms are the heavy halogen atoms (chlorine, bromine and iodine atoms).
[0055] [ka]
[0056] In formula (V), R 41 ~R 46 may be the same or different, and are a hydrogen atom, C 1 ~C 4 Alkyl group, C 2 ~C 4 Alkenyl group, C 2 ~C 4 Alkynyl group, C 1 ~C 4 Alkoxy group, C 1 ~C 4 It represents an alkylthio group, an aryl group, an aryloxy group, or an arylthio group.
[0057] In formula (V), R 41 ~R 46 may all be other than hydrogen atoms (e.g., methyl or ethyl groups), or R 41 ~R46 One of the groups may be a hydrogen atom and the remaining group may be other than a hydrogen atom (for example, a methyl group or an ethyl group).
[0058] The reducing agent is basically one that reduces tin fluoride in the tin-containing perovskite precursor solution to tin, but does not reduce tin heavy halide in the tin-containing perovskite precursor solution to tin, and is not limited to the reducing agent represented by any of the compounds represented by the above formulas (I) to (V). In addition, it is preferable that the reducing agent does not remain in the layer during the film formation process, or if it remains, it does not adversely affect the perovskite layer, or if it remains in a small amount, it improves the characteristics of the perovskite layer. As described above, the compounds represented by formulas (1) to (V) are reducing agents of the present invention that have such desirable characteristics. From a similar viewpoint, the following compounds are also considered to be effective as reducing agents of the present invention.
[0059] Germanium-based reducing agents An example of a germanium-based reducing agent is GeF 2 ,GeCl 2 ,GeBr 2 ,GeI 2 ,GeO,GeP,GeS,GeI 4 , and GeCl 4 It is.
[0060] Borane Reducing Agents An example of a borane reducing agent is BH 3 -THF and BH 3 -SMe 2 is
[0061] Aluminum-based reducing agents Examples of aluminum-based reducing agents are DIBAL-H (diisobutylaluminum hydride) and LAH (lithium aluminum hydride).
[0062] An example of a reducing agent other than those mentioned above is naphthaceno[5,6-cd:11,12-c',d']bis[1,2]dithiole (CAS number 193-44-2) or its derivatives (e.g., one or more hydrogen atoms in the ring of this compound are replaced by alkyl or alkoxy groups, or some of the carbon atoms in the ring are replaced by nitrogen or sulfur atoms).
[0063] Tin heavy halide An example of a solution containing a tin heavy halide (tin-containing perovskite precursor solution) is a solution containing a precursor for forming a tin-containing perovskite layer (tin-containing perovskite precursor solution). This solution contains, for example, tin fluoride as an additive. The content of tin fluoride is usually a trace amount. The tin heavy halide contains one or more types selected from tin iodide, tin bromide, and tin chloride.
[0064] The tin-containing perovskite compound used in the perovskite layer is known, and in this specification, a tin-containing perovskite compound containing Sn (tin) can be used as appropriate. The heavy tin halide is, for example, SnX m1 (X is one or more of I, Br, and Cl, and m1 is 1.8≦m1≦2.2). The tin heavy halide preferably contains tin iodide. The tin heavy halide may contain tin iodide, tin bromide, and tin chloride. For example, the tin heavy halide is mainly composed of tin iodide and tin bromide. In the tin-containing perovskite precursor solution, the tin heavy halide may be present in an ionized state as ions.
[0065] The tin heavy halide may be a tin-containing perovskite compound (also called the perovskite compound of the present invention) represented by formula (VI). RSnX j (VI) [In the formula, the oxidation number of Sn is 1.5 to 4. R represents at least one type of monovalent cation. X represents at least one type of heavy halogen atom. j represents 2.5 to 3.5.] The oxidation number of Sn is preferably 1.5 to 3.5, and may be 1.5 to 2.5, 1.8 to 2.2, or 1.5 to 2.
[0066] In the general formula (VI), R is at least one type of monovalent cation. R may be two or more types of cations. Examples of such monovalent cations include alkali metal cations and monovalent transition metal cations.
[0067] Examples of alkali metal cations are the sodium cation, the potassium cation, the cesium cation, and the rubidium cation.
[0068] Examples of monovalent transition metal cations are copper cation, silver cation, gold cation, iron cation, and ruthenium cation.
[0069] A specific example of R is R 51 NH 3+ The cation (R 51 represents a monovalent substituted or unsubstituted hydrocarbon group. A substituted hydrocarbon group means a hydrocarbon in which the hydrogen atoms of the hydrocarbon group are replaced by other atoms or substituents. Another specific example of R is:
[0070] NH 2 + =C(R 52 )-NH 2
[0071] (R 42 represents a hydrogen atom or a monovalent substituted or unsubstituted hydrocarbon group. It is a cation represented by the formula:
[0072] In this specification, examples of a "monovalent hydrocarbon group" are an alkyl group, an aryl group, or an aralkyl group.
[0073] The alkyl group is preferably a linear, branched or cyclic alkyl group having 1 to 20 carbon atoms. Specific examples of the alkyl group include a methyl group, an ethyl group, an n-propyl group, a 2-propyl group, an n-butyl group, a 1-methylpropyl group, a 2-methylpropyl group, a tert-butyl group, an n-pentyl group, a 1-methylbutyl group, a 1-ethylpropyl group, a tert-pentyl group, a 2-methylbutyl group, a 3-methylbutyl group, a 2,2-dimethylpropyl group, an n-hexyl group, a 1-methylpentyl group, a 1-ethylbutyl group, a 2-methylpentyl group, a 3-methylpentyl group, a 4-methylpentyl group, a 2-methylpentan-3-yl group, a 3,3-dimethylbutyl group, a 2, 2-dimethylbutyl group, 1,1-dimethylbutyl group, 1,2-dimethylbutyl group, 1,3-dimethylbutyl group, 2,3-dimethylbutyl group, 1-ethylbutyl group, 2-ethylbutyl group, n-heptyl group, n-octyl group, n-nonyl group, n-decyl group, n-undecyl group, n-dodecyl group, n-tridecyl group, n-tetradecyl group, n-pentadecyl group, n-hexadecyl group, n-heptadecyl group, n-octadecyl group, n-nonadecyl group, n-icosyl group, cyclopropyl group, cyclobutyl group, cyclopentyl group, and cyclohexyl group.
[0074] The "aryl group" is preferably an aryl group having a carbon number of 6 to 20. Examples of the aryl group include a phenyl group, an indenyl group, a pentalenyl group, a naphthyl group, an azulenyl group, a fluorenyl group, a phenanthrenyl group, an anthracenyl group, an acenaphthylenyl group, a biphenylenyl group, a naphthacenyl group, and a pyrenyl group.
[0075] The "aralkyl group" is preferably an aralkyl group having 7 to 20 carbon atoms. Examples of the aralkyl group include a benzyl group, a phenethyl group, a 1-phenylpropyl group, a 2-phenylpropyl group, a 3-phenylpropyl group, a 1-phenylbutyl group, a 2-phenylbutyl group, a 3-phenylbutyl group, a 4-phenylbutyl group, a 1-phenylpentylbutyl group, a 2-phenylpentylbutyl group, a 3-phenylpentylbutyl group, a 4-phenylpentylbutyl group, a 5-phenylpentylbutyl group, a 1-phenylhexylbutyl group, a 2-phenylhexylbutyl group, a 3-phenylhexylbutyl group, a 4-phenylhexylbutyl group, a 5-phenylhexylbutyl group, a 6-phenylhexylbutyl group, a 1-phenylheptyl group, a 1-phenyloctyl group, a 1-phenylnonyl group, a 1-phenyldecyl group, a 1-phenylundecyl group, a 1-phenyldodecyl group, a 1-phenyltridecyl group, and a 1-phenyltetradecyl group.
[0076] Examples of the "substituent" are the above-mentioned monovalent hydrocarbon groups, halogen atoms (e.g., fluorine atoms, chlorine atoms, bromine atoms, iodine atoms), -OR 1a (R 1a represents a hydrogen atom or the above monovalent hydrocarbon group), -SR 1b (R 1b represents a hydrogen atom or the above monovalent hydrocarbon group), a nitro group, an amino group, a cyano group, a sulfo group, a carboxy group, a carbamoyl group, an aminosulfonyl group, or an oxo group. The number of substituents, when present, is not particularly limited, and is preferably 10 or less, more preferably 5 or less, and even more preferably 3 or less.
[0077] R 51 and R 52 As the monovalent hydrocarbon group represented by the formula (I), from the viewpoint that the perovskite compound of the present invention is likely to have a three-dimensional structure, absorb light in a wider wavelength range, and easily improve the power conversion efficiency (PCE) and internal quantum efficiency (IQE), an alkyl group having 1 to 10 carbon atoms, an aryl group having 6 to 20 carbon atoms, and an aralkyl group having 7 to 12 carbon atoms are preferred, an alkyl group having 1 to 6 carbon atoms and an aryl group having 6 to 14 carbon atoms are more preferred, and an alkyl group having 1 to 4 carbon atoms is even more preferred. Also, for the same reason, R51 and R 52 As the alkyl group, an alkyl group is preferable, a linear or branched alkyl group is more preferable, and a linear alkyl group is further preferable. In particular, a methyl group is most preferable.
[0078] Above R 51 and R 52 The perovskite compound of the present invention is likely to have a three-dimensional structure, absorb light in a wider wavelength range, and improve the power conversion efficiency (PCE) and internal quantum efficiency (IQE). 51 is preferably a methyl group, and R 52 is preferably a hydrogen atom. In other words, R can be an alkali metal cation or a monovalent transition metal cation, or a CH 3 NH 3 + Alternatively, the following cations are preferred:
[0079] NH 2 + =CH-NH 2
[0080] The preferred R is CH 3 NH 3 -,(NH 2 ) 2 CH-, and (CH 3 NH 3 )x( (NH 2 ) 2 CH) 1-x - (x is a number from 0 to 1, preferably from 0.1 to 0.4, and may be from 0.2 to 0.3).
[0081] In the general formula (II), j is preferably 2.8 to 3.2 from the viewpoint of facilitating improvements in the power conversion efficiency (PCE) and the internal quantum efficiency (IQE).
[0082] An example of the perovskite compound of the present invention that satisfies these conditions is methylammonium tin iodide (CH 3 NH 3 SnI 3 : "MASnI3 "), (CH 3 NH 3 ) 2 Sn 3 I 8 : "MA 2 Sn 3 I 8 " and methyl ammonium tin bromide (CH 3 NH 3 SnBr 3 : "MASnBr 3 "), tin formamidinium iodide ((NH 2 ) 2 CHSnI 3 : "FASnI 3 "), and formamidinium tin bromide ((NH 2 ) 2 CHSnBr 3 : "FASnBr 3 "),FA 1-x MA x SnI 3 (x is a number from 0 to 1, preferably 0.1 to 0.4, and may be 0.2 to 0.3), CsSnI 3 ,CsSnBr 3 and mixtures of these. 0.7 5 MA 0.25 SnI 3 ,MASnI 3 and FASnI 3 is preferred.
[0083] In the following examples, the method for producing a perovskite layer using a tin heavy halide containing a trace amount of tin fluoride is mainly described. On the other hand, the reducing agent is, for example, ASnX 3 The scavenging effect of tin nanoparticles derived from tin fluoride is also expected in various tin-containing perovskite layers, such as those of the tin-containing perovskite type.
[0084] A solution containing a tin-containing perovskite compound can basically be obtained by dissolving a tin halide and a compound that serves as a source of halogenated cations in a solvent. The solvent is preferably a polar solvent, and more preferably an aprotic polar solvent. Examples of compounds that serve as a source of halogenated cations include FAI, MAI, FABr, MABr, and FA. 1-x MA x I,FA 1-x MA x The molar ratio of the tin halide to the compound serving as the source of halogenated cations may be 1:3 or more and 3:1, 1:2 to 2:1, 3:2 to 2:3, or 3:4 to 4:3.
[0085] The solvent preferably has a boiling point of about 35 to 250° C. Examples of the solvent include N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), sulfolane, N-methylpyrrolidone, propylene carbonate, α-acetyl-γ-butyrolactone, tetramethylene sulfoxide, ethyl cyanoacetate, acetylacetone, 3-methoxy N,N-dimethylpropanamide, N,N'-dimethylethyleneurea, 1,1,3,3-tetramethylurea, 2-acetylcyclohexanone, 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone, 3,4-dihydro-1(2H)-naphthalenone, cyclopentanone, cyclohexanone, cycloheptanone, aniline, piperidine, pyridine, Examples of suitable amines include 4-tert-butylpyridine, 4-amylpyridine, 4-aminopyridine, 2-amylpyridine, 4-methylpyridine, pentafluoropyridine, 2,4,6-tetramethylpyridine, 2,6-di-tert-butyl-4-methylpyridine, 4-pyridineethylamine, cyclooctanone, 2,5-dimethoxytetrahydrofuran, 1,4,7,10-tetraoxacyclododecane, ethyl p-toluate, 1,2-dimethoxybenzene, tetrahydrofurfuryl acetate, cyclohexyl acetate, cyclopentyl methyl ether, phenylethylamine, ethylenediamine, triethylamine, diisopropylethylamine, and hydrazine. Among these, N,N-dimethylformamide (DMF) or dimethylsulfoxide (DMSO) are preferred from the viewpoint of forming a coordinate bond at the metal center.
[0086] An example of the concentration of the tin halide in the solvent is 0.1 to 5 mol / L (or 0.5 to 3 mol / L). A solution containing a tin-containing perovskite compound can be obtained by appropriately mixing the above-mentioned compound with the above-mentioned solvent. If necessary, the solvent may be appropriately stirred and heated to dissolve the compound.
[0087] substrate As the substrate, a known substrate for a perovskite solar cell or an organic EL element can be appropriately used. Examples of the substrate are a glass substrate, an insulating substrate, a semiconductor substrate, a metal substrate, and a conductive substrate (including a conductive film). In addition, a substrate having at least one film of a metal film, a semiconductor film, a conductive film, and an insulating film formed on a part or all of the surface of the substrate can also be preferably used.
[0088] Examples of the constituent metals of the metal film include one or more metals selected from gallium, iron, indium, aluminum, vanadium, titanium, chromium, rhodium, nickel, cobalt, zinc, magnesium, calcium, silicon, yttrium, strontium, and barium. Examples of the constituent materials of the semiconductor film include simple elements such as silicon and germanium, compounds containing elements of groups 3 to 5 and groups 13 to 15 of the periodic table, metal oxides, metal sulfides, metal selenides, and metal nitrides. Examples of the constituent materials of the conductive film include tin-doped indium oxide (ITO), fluorine-doped indium oxide (FTO), zinc oxide (ZnO), aluminum-doped zinc oxide (AZO), gallium-doped zinc oxide (GZO), tin oxide (SnO 2 ), indium oxide (In 2 O 3 ), tungsten oxide (WO 3 An example of the insulating film is aluminum oxide (Al 2 O 3 ), titanium dioxide (TiO 2 ), silicon oxide (SiO 2 ), silicon nitride (Si 3 N 4 ), silicon oxynitride (Si 4 O 5 N 3 ).
[0089] Examples of the shape of the substrate include a plate-like shape such as a flat plate or a disk, a fiber-like shape, a rod-like shape, a cylindrical shape, a prismatic shape, a cylindrical shape, a spiral shape, a spherical shape, a ring shape, and a porous structure. Of these, a plate-like substrate is preferred. Examples of the thickness of the substrate are preferably 0.1 μm to 100 mm, and more preferably 1 μm to 10 mm.
[0090] Applying a solution containing a tin-containing perovskite compound to a substrate. When applying a solution containing a tin-containing perovskite compound to a substrate, a semiconductor layer serving as an underlayer may be formed on the substrate. In this case, applying a solution containing a tin-containing perovskite compound to a substrate means a process of applying a solution containing a tin-containing perovskite compound to (onto) the substrate on which the underlayer has been formed.
[0091] In order to apply the solution containing the tin-containing perovskite compound to the substrate, spin coating, dip coating, screen printing, roll coating, die coating, transfer printing, spraying, or slit coating may be used. Among these, it is preferable to apply the solution to the substrate by spin coating. Spin coating is a method in which the solution is dropped onto the substrate while rotating it, and the solution is applied to the substrate. The substrate carrying the solution may also be rotated to apply the solution to the substrate. The rotation speed may be a maximum speed of 1,000 to 10,000 rpm for 30 seconds to 5 minutes, 2 to 15 seconds to reach the maximum speed, and 1 to 15 seconds from the maximum speed to stop.
[0092] Next, we will explain the process of applying a poor solvent to the substrate.
[0093] A poor solvent means a solvent that has the ability to dissolve a solute but does not have a high solubility for the solute. Examples of poor solvents include substituted aliphatic hydrocarbons such as dichloromethane and chloroform; aromatic hydrocarbons such as toluene and benzene; substituted aromatic hydrocarbons such as chlorobenzene, orthodichlorobenzene, and nitrobenzene; acetic acid; ethers such as diethyl ether and tetrahydrofuran (THF); alcohols such as methanol, ethanol, isopropanol, butanol, and octanol; long-chain hydrocarbons such as hexane (especially C4-10 hydrocarbons); and acetonitrile. These poor solvents can be used alone or in combination of two or more. Among these, chlorobenzene or toluene is preferred.
[0094] The poor solvent may be used alone or in combination with a polar solvent. When the poor solvent is mixed with a polar solvent, the ratio of the polar solvent to the poor solvent (poor solvent / polar solvent) is preferably 2.0 to 10.0 / 1.0 (volume ratio), and more preferably 3.0 to 8.0 / 1.0 (volume ratio).
[0095] When applying the poor solvent, since the tin-containing perovskite compound is applied to the substrate, applying the poor solvent to the substrate means applying the poor solvent to the substrate in a state in which the tin-containing perovskite compound is applied. The method of applying the poor solvent to the substrate is the same as the method of applying the tin-containing perovskite compound. Note that, when applying the tin-containing perovskite compound by spin coating, the poor solvent may be applied to the substrate by dropping the poor solvent onto the substrate. The amount of the poor solvent applied may be appropriately adjusted. The volume ratio of the solution containing the tin-containing perovskite compound to the poor solvent may be 1:10 to 2:1, or 1:5 to 1:1.
[0096] The temperature of the poor solvent when applying the poor solvent to the substrate is preferably 45°C or higher and 100°C or lower. Under the conditions shown in the examples described later, when a poor solvent at this temperature is used, crystal growth from the seed crystals can be suppressed and the formation of the seed crystals can be promoted, so that the tin-containing perovskite layer can be filled, the unevenness of the tin-containing perovskite layer can be reduced, and a flat tin-containing perovskite layer can be obtained. In this method, the temperature of the poor solvent may be 45°C or higher and 85°C or lower, or 50°C or higher and 70°C or lower. At this temperature, the tin-containing perovskite compound can be grown without damaging the underlayer. The temperature of the poor solvent may be appropriately adjusted depending on the type of the tin-containing perovskite compound, etc.
[0097] The poor solvent is applied by dropping the poor solvent while rotating the substrate, and the rotation is preferably stopped within 0.5 to 7.5 seconds (for example, 1 to 7 seconds, 1 to 6 seconds) after the poor solvent is applied. As demonstrated by the examples described later, the state of the tin-containing perovskite compound can be adjusted by stopping the rotation very quickly after dropping the poor solvent. Conventionally, the rotation speed of the substrate is usually maintained for about 30 seconds after dropping the poor solvent, and then the rotation of the substrate is decelerated. In this specification, as shown by the examples described later, it is preferable to start decelerating the rotation speed of the substrate immediately to within 10 seconds (within 5 seconds immediately after, within 3 seconds immediately after, within 2 seconds immediately after, within 1 second immediately after, or immediately after) after the poor solvent is dropped. In this way, the variation in characteristics in the perovskite layer (film) can be suppressed.
[0098] In addition, the step of applying the solution containing the tin-containing perovskite compound and the step of applying the poor solvent are preferably performed in a closed system, similar to the annealing treatment step described later. In the closed system, it is preferable that the vapor of the solvent contained in the solution containing the tin-containing perovskite compound is present, and more preferably, the solvent is at a saturated vapor pressure or a partial pressure of 90% or more of the saturated vapor pressure in the closed system.
[0099] Next, the process of annealing the substrate will be described. Annealing refers to a process of heating the substrate. The annealing process is preferably carried out promptly after the poor solvent is dropped or after the substrate is stopped. As shown in the examples described below, the annealing process preferably includes a process of gradually heating the substrate in a closed system containing solvent vapor. In the closed system, it is preferable that the vapor of the solvent contained in the solution containing the tin-containing perovskite compound is present, and more preferably, the solvent is at saturated vapor pressure or a partial pressure of 90% or more of the saturated vapor pressure in the closed system.
[0100] The step of annealing the substrate preferably involves increasing the temperature in two or more stages, which, as demonstrated in the examples, can promote the growth of the tin-containing perovskite compound and increase the grain size, thereby filling the tin-containing perovskite layer.
[0101] When the annealing process includes multiple stages, this means that the substrate temperature is raised to multiple target temperatures, maintained at the set temperatures for a predetermined period of time, and then raised to the next set temperature. An example of the set temperature for the first stage is 30°C or higher and 60°C or lower, or may be 35°C or higher and 55°C or lower, or 40°C or higher and 50°C or lower. The residence time at the set temperature of the first stage may be from 5 seconds to 1 minute, or from 5 minutes to 20 minutes. The set temperature of the second stage is preferably higher than that of the first stage. An example of the set temperature of the second stage is 50°C or higher and 80°C or lower, or may be 55°C or higher and 75°C or lower, or may be 60°C or higher and 70°C or lower. The residence time at the set temperature in the second stage may be from 5 seconds to 1 minute, from 5 minutes to 30 minutes, from 5 minutes to 20 minutes, or from 10 minutes to 20 minutes. The set temperature of the third stage (if the first or second stage is omitted, the set temperature of the second stage) is preferably higher than the set temperature of the first or second stage. An example of the set temperature of the third stage is 70°C or higher and 120°C or lower, or may be 80°C or higher and 110°C or lower, or may be 90°C or higher and 110°C or lower. The residence time at the set temperature in the third stage may be from 5 seconds to 1 minute, or from 5 minutes to 20 minutes. An example of the thickness of the perovskite layer that can be obtained in this manner is 10 nm to 1000 nm. The thickness may be 50 nm to 500 nm, 100 nm to 500 nm, or 250 nm to 500 nm.
[0102] After obtaining a perovskite layer by the above-mentioned method for producing a perovskite layer, a perovskite solar cell can be produced according to a normal method. However, since the perovskite layer can also be used for producing an organic EL element, after obtaining a perovskite layer by the above-mentioned method for producing a perovskite layer, an organic EL element can be produced using the perovskite layer.
[0103] The following invention described in this specification relates to a perovskite layer and a perovskite type solar cell including the perovskite layer. The perovskite layer includes a tin-containing perovskite compound, and the coverage rate of the tin-containing perovskite compound is preferably 95% or more and 100% or less. The coverage rate is more preferably 98% or more and 100% or less, and more preferably 99% or more and 100% or less. However, as long as the characteristics are not impaired, even if the coverage rate is 95% or more and 100%, it is preferable because the coverage rate is higher than that when manufactured based on the conventional technology. In this perovskite layer, it is preferable that the average particle size of the tin-containing perovskite compound is 150 nm or more and 500 nm or less. The coverage rate may be calculated by taking an SEM image and calculating the area. Specifically, the coverage rate may be determined using image analysis software, or the coverage rate, which is the percentage of the area of the substrate covered by the perovskite compound, may be determined by surrounding the black area not covered by the perovskite compound and determining the area of the surrounded portion. The average particle size of the tin-containing perovskite compound may also be determined by photographing the tin-containing perovskite layer and using the tin-containing perovskite compound boundary surface to determine the average size (for example, the average value of the maximum length of the boundary surface). The average particle size may be determined by using the arithmetic mean value.
[0104] 2. Perovskite solar cells A perovskite solar cell comprises, for example, a transparent electrode, a (hole) blocking layer, an electron transport layer, a perovskite layer (light absorption layer), a hole transport layer, and a metal electrode in this order. A perovskite solar cell may be a forward type in which an n-type semiconductor layer is provided on a transparent electrode, or a reverse type in which a p-type semiconductor layer is provided on a transparent electrode. Below, a perovskite solar cell is explained using as an example a perovskite solar cell that comprises, in this order, a transparent electrode, a (hole) blocking layer, an electron transport layer, a perovskite layer (light absorption layer), a hole transport layer, and a metal electrode.
[0105] 2.1.Transparent electrode Since the transparent electrode is a support for the electron transport layer and also has the function of extracting current (electrons) from the perovskite layer (light absorption layer) via the (hole) blocking layer, a conductive substrate is preferred, and a transparent conductive layer that is translucent and can transmit light that contributes to photoelectric conversion is preferred.
[0106] Examples of the transparent conductive layer include tin-doped indium oxide (ITO) film and impurity-doped indium oxide (In 2 O 3 Examples of the transparent conductive layer include a transparent conductive film, an impurity-doped zinc oxide (ZnO) film, a fluorine-doped tin dioxide (FTO) film, and a laminated film formed by laminating these. The thickness of these transparent conductive layers is not particularly limited, and it is usually preferable to adjust the resistance to 5 to 15 Ω / □ (per unit area). The transparent conductive layer can be obtained by a known film formation method depending on the material to be formed.
[0107] The transparent conductive layer may be covered with a light-transmitting covering body as necessary to protect it from the outside. Examples of the light-transmitting covering body include resin sheets such as fluororesin, polyvinyl chloride, polyimide, etc.; inorganic sheets such as white plate glass, soda glass, etc.; and hybrid sheets made by combining these materials. There are no particular limitations on the thickness of these light-transmitting covering bodies, and it is usually preferable to adjust the resistance to 5 to 15 Ω / □.
[0108] 2.2. (Hole) blocking layer The (hole) blocking layer is a layer provided to prevent leakage of holes and suppress reverse current to improve solar cell characteristics (particularly photoelectric conversion efficiency), and is preferably provided between the transparent electrode and the perovskite layer (light absorbing layer). The (hole) blocking layer is preferably a layer made of a metal oxide such as titanium oxide, and compact TiO 2 A layer in which the surface of the transparent electrode is smoothly and densely covered with an n-type semiconductor such as ZnO is more preferable. "Dense" means that the metal compound is packed at a higher density than the packing density of the metal compound in the electron transport layer. Note that pinholes, cracks, etc. may be present as long as the transparent electrode and the electron transport layer are not electrically connected.
[0109] The thickness of the (hole) blocking layer is, for example, 5 to 300 nm. From the viewpoint of the efficiency of electron injection into the electrode, the thickness of the (hole) blocking layer is more preferably 10 to 200 nm.
[0110] The (hole) blocking layer is formed on the transparent electrode. When a metal oxide is used for the (hole) blocking layer, it can be prepared by performing spray pyrolysis according to a known method (e.g., Non-Patent Document 4, J. Phys. D: Appl. Phys. 2008, 41, 102002, etc.). For example, it can be prepared by spraying an alcohol solution (e.g., isopropyl alcohol solution, etc.) of 0.01 to 0.40 M (especially 0.02 to 0.20 M) of metal alkoxide (titanium alkoxide such as titanium di(isopropoxide)bis(acetylacetonate)) onto a transparent electrode placed on a hot plate heated to 200 to 550°C (especially 300 to 500°C).
[0111] The resulting substrate was then coated with titanium oxide (TiO 2 etc.), titanium alkoxides (titanium isopropoxide etc.), titanium halides (TiCl 4 It is also possible to make a denser film by immersing the film in an aqueous solution of the above-mentioned compound (e.g., ethyl acetate, ethyl acetate diethyl ether, etc.) and heating it.
[0112] The concentration of the raw material in the aqueous solution containing the raw material for the (hole) blocking layer is preferably 0.1 to 1.0 mM, more preferably 0.2 to 0.7 mM. The immersion temperature is preferably 30 to 100° C., more preferably 50 to 80° C. Furthermore, the heating conditions are preferably 200 to 1000° C. (particularly 300 to 700° C.) and 5 to 60 minutes (particularly 10 to 30 minutes).
[0113] 2.3.Electron transport layer The electron transport layer is formed to increase the active surface area of the perovskite layer (light absorption layer), improve the photoelectric conversion efficiency, and facilitate electron collection. The electron transport layer may be formed on a substrate, but is preferably formed on a (hole) blocking layer. The (hole) blocking layer may also function as the electron transport layer, or the electron transport layer may also function as the (hole) blocking layer. The electron transport layer may be a flat layer made of an organic semiconductor material such as a fullerene derivative. The electron transport layer may also be made of titanium oxide (TiO 2 ) (mesoporous TiO 2 (including SnO 2 The electron transport layer may be a mesoporous TiO 2 It is preferable that the porous structure has a porous property as a whole, for example, by gathering granular bodies, needle-shaped bodies, tubular bodies, columnar bodies, etc. In addition, the pore size is preferably nanoscale. By having a porous structure, since it is nanoscale, the active surface area of the light absorption layer is significantly increased, and the solar cell characteristics (particularly photoelectric conversion efficiency) are improved, and a porous electron transport layer with excellent electron collection can be formed.
[0114] The electron transport layer may be a layer made of a metal oxide such as titanium oxide or tin oxide. If the metal compound is a semiconductor, it may be doped with a donor when using a semiconductor. This allows the electron transport layer to function as a window layer for introduction into the perovskite layer (light absorbing layer), and allows the power obtained from the perovskite layer (light absorbing layer) to be extracted more efficiently.
[0115] The thickness of the electron transport layer is not particularly limited, and is preferably about 10 to 300 nm, more preferably about 10 to 250 nm, from the viewpoint of being able to collect more electrons from the perovskite layer (light absorbing layer). The electron transport layer can be obtained by using a known film forming method according to the material to be molded. For example, it can be produced by applying an alcohol solution (e.g., ethanol solution, etc.) of 5 to 50 mass % (particularly 10 to 30 mass %) of titanium oxide paste on the (hole) blocking layer. Known or commercially available titanium oxide pastes can be used. The coating method is preferably spin coating. Coating can be performed at about 15 to 30°C, for example.
[0116] 2.4. Perovskite layer (light absorbing layer) The perovskite layer (light absorbing layer) in a perovskite solar cell is a layer that absorbs light and transfers excited electrons to perform photoelectric conversion. The perovskite layer (light absorbing layer) contains a perovskite material or a perovskite complex. The perovskite layer may be manufactured based on the method described above. It is preferable to realize mass production of the perovskite layer by roll-to-roll. It is preferable to apply the mixed liquid onto the substrate by spin coating, dip coating, screen printing, roll coating, die coating, transfer printing, spraying, slit coating, or the like, preferably by spin coating.
[0117] The tin-containing perovskite layer will be described below. The tin-containing perovskite layer has a tin content of 100% Sn, which is the percentage of the tetravalent tin atomic content in the total of the tetravalent tin atomic content and the divalent tin atomic content in the first measurement region, which is a region at a depth of 20 nm from the center of the surface of the tin-containing perovskite layer. +4 20nm The value is between 0.1% and 5%.
[0118] The tin-containing perovskite layer means a perovskite layer that contains tin. The perovskite layer is usually rectangular. Therefore, the central part of the surface of the tin-containing perovskite layer means the vicinity of the center of gravity of the surface.
[0119] The first measurement region, which is a region 20 nm deep in the center of the surface, refers to the center of the surface of the perovskite layer that is exposed by etching the surface of the perovskite layer to remove 20 nm, as described below. Etching may be performed in an oxygen-free atmosphere (e.g., in a vacuum). An example of etching is argon etching.
[0120] Sn +4 20nm The value is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin in the first measurement region. The atomic content of tetravalent tin and the atomic content of divalent tin can be obtained by separating peaks corresponding to divalent tin and tetravalent tin from the spectrum obtained by X-ray photoelectron spectroscopy (XPS) measurement and calculating the area. In addition, Gaussian fitting may be performed for peak separation, and the area may be calculated automatically using known software or programs. In other words, Sn +4 20nm The value is calculated using the following formula: Sn +4 20nm Value = 100 x (atomic content of tetravalent tin) / ((atomic content of divalent tin) + (atomic content of tetravalent tin))
[0121] As demonstrated by the examples described below, Sn +4 20nm If the value is 0.1% or more and 5% or less, the proportion of tetravalent tin is reduced, and the photoelectric conversion efficiency is significantly increased while maintaining various physical properties. +4 20nm The value is preferably 0.1% or more and 3% or less. +4 20nm The value may be 0.6% or more and 2.4% or less, 0.8% or more and 2% or less, or 1% or more and 1.4% or less. By fine-tuning the manufacturing conditions with reference to the examples described later, Sn +4 20nm You can tweak the values.
[0122] A preferred example of the tin-containing perovskite layer is Sn +4 40nm The value is 0% or more and 0.5% or less. +4 40nm The value may be 0% or more and 0.3% or less, 0.1% or more and 0.3% or less, 0% or more and 0.2% or less, or 0% or more and 0.1% or less. Sn +4 40nm The value is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin in the second measurement area, which is a region 40 nm deep from the center of the surface of the tin-containing perovskite layer. The second measurement area, which is a region 40 nm deep from the center of the surface, refers to the center of the surface of the perovskite layer that is exposed by etching the surface of the perovskite layer to remove 40 nm. Sn +4 40nm The value is Sn +4 20nm The value can be calculated in the same manner.
[0123] A preferred example of the tin-containing perovskite layer is Sn +4 表面 value and Sn +4 20 nm Ratio to value (Sn +4 表面 Value / Sn +4 20nm The ratio (value) may be 5 or more and 20 or less, 6 or more and 10 or less, or 10 or more and 20 or less. Sn +4 表面 The value is the percentage of the atomic content of tetravalent tin in the total atomic content of tetravalent tin and divalent tin at the center of the surface of the tin-containing perovskite layer. +4 表面 value and Sn +4 20nm The ratio of the value to Sn +4 表面 Value / Sn +4 2 0nm It can be calculated by the value. A preferred example of the tin-containing perovskite layer is Sn +4 表面 value and Sn +4 40 nm Ratio to value (Sn +4 表面 Value / Sn +4 40nm The ratio (value) may be 3 or more. This ratio may be 5 or more, 8 or more, or 10 or more.
[0124] Among the above-mentioned tin-containing perovskite layers, a preferred example is a layer containing lead atoms (Pb +2 ) is a Pb-Sn mixed perovskite layer containing tin atoms (Sn +2 and Sn +4 The total content of lead atoms (Pb +2 The atomic content of ) is preferably 0% or more and 900% or less, more preferably 0% or more and 200% or less, and further preferably 0% or more and 100% or less.
[0125] Among the above-mentioned tin-containing perovskite layers, preferred examples from the viewpoint of reducing the environmental load are those that do not contain any lead atoms, or, if they contain lead atoms, contain lead atoms in an amount of 1 / 10 or less of the amount of tin atoms. Even if the amount of lead atoms is small, as shown in the following examples, it is possible to obtain a perovskite layer having desirable properties. However, lead may be contained at the level of an impurity.
[0126] The thickness of the perovskite layer (light absorbing layer) is preferably, for example, 50 to 1000 nm, more preferably 200 to 800 nm, from the viewpoint of the balance between the light absorption efficiency and the exciton diffusion length, and the absorption efficiency of the light reflected by the transparent electrode. The thickness of the perovskite layer (light absorbing layer) of the present invention is preferably within the range of 100 to 1000 nm, more preferably within the range of 250 to 500 nm. Specifically, the lower limit of the thickness of the perovskite layer (light absorbing layer) of the present invention is preferably 100 nm or more (particularly 250 nm) or more, and the upper limit is preferably 1000 nm or less (particularly 500 nm or less). The thickness of the perovskite layer (light absorbing layer) of the present invention is measured by a cross-sectional scanning electron microscope (cross-sectional SEM) of a film made of the complex of the present invention.
[0127] The flatness of the perovskite layer (light absorbing layer) of the present invention is preferably such that the height difference is 50 nm or less (-25 nm to +25 nm) in a range of 500 nm x 500 nm in the horizontal direction of the surface measured by a scanning electron microscope, and more preferably the height difference is 40 nm or less (-20 nm to +20 nm). This makes it easier to balance the light absorption efficiency and the exciton diffusion length, and the absorption efficiency of the light reflected by the transparent electrode can be further improved. The flatness of the perovskite layer (light absorbing layer) is measured by a cross-sectional scanning electron microscope (cross-sectional SEM) of the perovskite layer (light absorbing layer) of the present invention, with an arbitrarily determined measurement point as the reference point, the difference with the largest film thickness within the measurement range as the upper limit, and the difference with the smallest film thickness as the lower limit.
[0128] This tin-containing perovskite layer contains one or more selected from zero-valent tin, pyrazine-based compounds, silicon-based compounds, and germanium-based compounds in a total amount of 0.01 ppm to 1000 ppm. This tin-containing perovskite layer can be obtained based on the above-mentioned method for producing a tin-containing perovskite layer, and a predetermined amount of residues such as reducing agents are present. The tin-containing perovskite layer has excellent passivation properties due to the presence of a predetermined amount of specific substances. The contents of these substances can be analyzed by performing a component analysis on the tin-containing perovskite layer. In the examples described below, a tin-containing perovskite layer is actually obtained. The above contents have a criticality (there is a significant difference in passivation between outside and within the above numerical range). Examples of pyrazine-based compounds and silicon-based compounds are compounds represented by formulas (I) to (V). The germanium-based compound is a compound produced by reacting the germanium-based reducing agent described above or a compound in the solution with the reducing agent. The total amount may be 0.1 ppm or more and 500 ppm or less, or 1 ppm or more and 500 ppm or less. A luminescent material or a photoelectric conversion element having such a tin-containing perovskite layer will have good characteristics by utilizing the above characteristics.
[0129] 2.5. Hole transport layer The hole transport layer is a layer that has the function of transporting charges. For example, a conductor, a semiconductor, an organic hole transport material, etc. can be used for the hole transport layer. The material can function as a hole transport material that receives holes from the perovskite layer (light absorption layer) and transports the holes. The hole transport layer is formed on the perovskite layer (light absorption layer). Examples of the conductor and semiconductor include CuI and CuInSe 2 Compound semiconductors containing monovalent copper such as CuS; GaP, NiO, CoO, FeO, Bi 2 O 3 ,MoO 2 ,Cr 2 O 3Examples of the organic hole transport material include compounds containing metals other than copper, such as CuI, etc. Among them, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility, semiconductors containing monovalent copper are preferred, and CuI is more preferred. Examples of the organic hole transport material include polythiophene derivatives such as poly-3-hexylthiophene (P3HT) and polyethylenedioxythiophene (PEDOT); fluorene derivatives such as 2,2',7,7'-tetrakis-(N,N-di-p-methoxyphenylamine)-9,9'-spirobifluorene (spiro-OMeTAD); carbazole derivatives such as polyvinylcarbazole; triphenylamine derivatives such as poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA); diphenylamine derivatives; polysilane derivatives; and polyaniline derivatives. Among them, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility, triphenylamine derivatives, fluorene derivatives, etc. are preferred, and PTAA, spiro-OMeTAD, etc. are more preferred.
[0130] In order to further improve the hole transport properties, lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), silver bis(trifluoromethylsulfonyl)imide, trifluoromethylsulfonyloxysilver, and NOSbF are added to the hole transport layer. 6 ,SbCl 5 ,SbF 5 The hole transport layer may contain an oxidizing agent such as t-butylpyridine (TBP), 2-picoline, 2,6-lutidine, etc. The hole transport layer may also contain a basic compound such as t-butylpyridine (TBP), 2-picoline, 2,6-lutidine, etc. The content of the oxidizing agent and the basic compound may be the amount that has been conventionally used. The thickness of the hole transport layer is preferably, for example, 30 to 200 nm, more preferably 50 to 100 nm, from the viewpoint of more efficiently receiving only holes and obtaining higher hole mobility. The method of forming the hole transport layer is preferably, for example, performed under a dry atmosphere. For example, it is preferable to apply (spin coat, etc.) a solution containing an organic hole transport material on a perovskite layer (light absorbing layer) under a dry atmosphere, and heat it at 30 to 150°C (particularly 50 to 100°C).
[0131] 2.6. Metal electrode The metal electrode is disposed opposite the transparent electrode and formed on the hole transport layer, thereby enabling the exchange of charges with the hole transport layer. As the metal electrode, a known material used in the industry can be used, and examples of the metal electrode include metals such as platinum, titanium, stainless steel, aluminum, gold, silver, nickel, etc., or alloys thereof. Among these, the metal electrode is preferably made of a material that can be formed by a method such as vapor deposition, since the electrode can be formed in a dry atmosphere. Perovskite solar cells having layer configurations other than those described above can also be manufactured by the same method.
[0132] 3. Organic electroluminescence element (organic EL element) The organic EL element is a publicly known element, as described in, for example, JP 2017-123352 A and JP 2015-071619 A, and its manufacturing method is also publicly known. An example of an organic EL element has a substrate, an anode, a cathode, and an organic layer disposed between the anode and the cathode. The organic layer is configured by stacking, in this order from the anode side, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, and an electron injection layer. The compound of the present invention can be used as an electron transport material in the electron transport layer.
[0133] 4. Manufacturing method of solar cells The present invention also provides a method for manufacturing a solar cell, which includes the steps of forming an electron transport (blocking) layer on a substrate using the above-described method for manufacturing a perovskite layer, forming a perovskite layer on the electron transport layer, forming a hole transport layer on the perovskite layer, and forming an electrode on the hole transport layer.
[0134] 5. Purification method for heavy halide tin-containing materials Certain aspects of the invention described herein include 4+ In addition to removing Sn 2+ Sn 4+The present invention relates to a method for purifying a tin heavy halide-containing substance, which is adjusted so as to be less likely to be oxidized to SnO. The method includes a reducing agent addition step of adding a reducing agent to a tin heavy halide solution containing impurities, and an acquisition step of acquiring a tin heavy halide-derived substance after the reducing agent addition step. The tin heavy halide and the reducing agent are as described above. The tin heavy halide solution contains tin fluoride as an additive. The impurities are SnO. 2 or SnX 4 The tin fluoride may contain tetravalent tin ions resulting from a species or the like, or may contain both tin fluoride and tetravalent tin ions.
[0135] The method for purifying a heavy halide tin-containing material includes a reducing agent addition step, a precipitate removal step for removing a precipitate, and The method may further include, after the precipitate removal step, a step of leaving the solution from which the precipitate has been removed still. The obtaining step may include a crystal obtaining step of obtaining the crystals precipitated by the leaving step.
[0136] Tin Dihalide Solution One embodiment of the invention described in this specification relates to a solution containing tin heavy halide, tin fluoride, and a reducing agent, which can provide a precursor solution for a tin-containing perovskite layer or a high-purity tin heavy halide-containing material. For example, the perovskite precursor solution described above functions as a tin heavy halide solution. High-purity tin heavy halide: SnX 2 (X = Cl, Br, I) is difficult to produce, e.g., SnO 2 or SnX 4 Tetravalent tin ion species such as Sn 4+ ) impurities such as heavy tin halides and SnF 2 In the mixed system with SnF 2 By reducing Sn, nanoparticles derived from Sn are generated, and these nanoparticles function as scavengers. 2 SnX 4This effectively prevents the tin heavy halide from being oxidized to a high degree. As a result, a highly pure tin heavy halide-containing substance can be obtained. The tin heavy halide-containing substance may be a tin heavy halide or a compound that contains a tin heavy halide as part of its composition.
[0137] This solution contains a tin heavy halide, a tin fluoride, and a reducing agent. The tin heavy halide and the reducing agent are as described above. In addition to the tin fluoride, this solution may contain tetravalent tin ions as an impurity. This solution may be used as a tin-containing perovskite precursor solution. The concentration of the reducing agent used in this tin-containing perovskite precursor solution may be lower than the concentration of the tin fluoride used in the tin-containing perovskite precursor solution.
[0138] Working Example The present invention will be specifically described below using examples. The present invention is not limited to the above description or examples, and may include matters that are obvious to those skilled in the art.
[0139] In the examples described below, the following equipment was used: Photoluminescence (PL) spectrum measurement: Picosecond laser pulse (wavelength 444nm or 688nm, Advanced Laser Diode Systems, Inc.) Nitrogen-cooled CCD camera (Princeton Instruments, Inc.)
[0140] Time-resolved PL measurements Avalanche photodiode (ID Quantique, Inc.) Time-correlated single-photon counting board (Becker & Hickl, Inc.)
[0141] JV measurement OTENTO-SUN-P1G (BUNKOUKEIKI Co., Ltd.) Keithley 2400
[0142] IPCE measurement SM-250 diffuse reflection unit (BUNKOUKEIKI Co., Ltd.)
[0143] SEM observation S8010 (Hitachi High-Technologies Co., Ltd)
[0144] 119 Sn NMR measurement Bruker Avance III 600US Plus NMR
[0145] TEM observation JEM-1011 (JEOL Co., Ltd.) EXAMPLES
[0146] Optical properties of tin-containing perovskite films In a glove box (Ar gas, H 2 O < 0.1 ppm, H 2 Approximately 200 μL of perovskite precursor solutions (1) and (2) prepared as described below were applied to a quartz substrate at 1000 rpm (O <0.1 ppm), and 300 μL of chlorobenzene heated to 65 °C was dropped onto the substrate during spin coating to obtain a brown film (5 s ramp at 5000 rpm, 60 s spin coating, chlorobenzene was dropped between the last 2 s and 1 s, and the slope was stopped at 1 s). The brown film obtained was annealed at 45 °C for 10 min, 65 °C for 10–30 min, and then 100 °C for 5 min and 100 °C for 30 min to obtain a black perovskite film.
[0147] The obtained perovskite film was placed in a sample case filled with argon, and photoluminescence (PL) spectrum measurements and time-resolved PL measurements were performed. A picosecond laser pulse (wavelength 444 nm or 688 nm, Advanced Laser Diode Systems, Inc.) was used as the excitation light for the measurements. The excitation density at the sample position was 127 nJ / cm. 2 The measurements were performed under weak excitation conditions. PL spectra were measured using a spectrometer and a nitrogen-cooled CCD camera (Princeton Instruments, Inc.). In the time-resolved PL measurements, PL from the sample was detected with an avalanche photodiode (ID Quantique, Inc.), and time-resolved decay curves were obtained using a time-correlated single-photon counting board (Becker & Hickl, Inc.).
[0148] From the PL and time-resolved PL measurements, reducing agent 1 was found to be SnI 2 When reducing agent 1 was added at 0.1 mol% to SnI, the fluorescence lifetime was extended from 6.0 ns to 7.3 ns while maintaining the fluorescence wavelength (Figures 1 and 2). 2 The fluorescence wavelength shifts to the short wavelength side when the amount of SnF added is 10.0 mol%. This is due to the additive SnF 2 In addition, when reducing agent 2 was added, the fluorescence lifetime was significantly increased while maintaining the fluorescence wavelength, and the SnI 2 It was revealed that the time-series peak was extended to 14 ns when 1.0 mol% of Sn was added to the 4+ This result suggests that by forming a film using a solution containing reducing agents 1 and 2 as seed scavengers, the recombination of carriers generated by photoexcitation was suppressed while maintaining the structure and composition of the perovskite compound.
[0149] The perovskite precursor solutions (1) and (2) were obtained as follows. [ka]
[0150] Precursor solution (1): Perovskite precursor solution with reducing agent 1 added SnI in a glove box 2 (1341 mg, 3.6 mmol),FAI (464 mg, 2.7 mmol),MAI (143 mg, 0.9 mmol),SnF 2 (56 mg, 0.36 mmol) was dissolved in ultra-dehydrated DMSO (4.0 mL) at 45 °C. After stirring at 45 °C for 1 h, the mixture was filtered through a PTFE filter and FA was obtained. 0.75 MA 0.25 SnI 3 A precursor solution was prepared. 1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (1) (7.9 mg, 0.035 mmol) was dissolved in DMF (50 μL) at 65°C. 0.75 MA 0.25 SnI 3 The precursor solution was dripped with 1.3 μL of reducing agent 1. The addition of reducing agent 1 resulted in the formation of yellow FA. 0.75 MA 0.25 SnI 3 The precursor solution turned into a dark green suspension. After stirring for 15 min at 45 °C, the suspension turned yellow again and a precipitate with a metallic luster was formed. The precipitate was removed by filtration using a PTFE filter, and the precursor solution (SnI 2 In the same manner, reducing agent 1 was replaced with SnI 2 Solutions were obtained in which 1.0 and 10.0 mol % of the compound was added.
[0151] Precursor solution (2): Perovskite precursor solution with added reducing agent 2 SnI in a glove box 2 (1341 mg, 3.6 mmol),FAI (464 mg, 2.7 mmol),MAI (143 mg, 0.9 mmol),SnF 2 (56 mg, 0.36 mmol) was dissolved in ultra-dehydrated DMSO (4.0 mL) at 45 °C. After stirring at 45 °C for 1 h, the mixture was filtered through a PTFE filter and FA was obtained.0.75 MA 0.25 SnI 3 A precursor solution (0.9 M) was prepared by dissolving 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (2) (9.9 mg, 0.035 mmol) in DMF (50 μL) at 65 °C. 0.75 MA 0.25 SnI 3 The precursor solution was dripped with 1.3 μL of reducing agent 2. The addition of reducing agent 2 resulted in the formation of yellow FA. 0.75 MA 0.25 SnI 3 The precursor solution turned into a dark green suspension. After stirring for 15 min at 45 °C, the suspension turned into a yellow solution again and a precipitate formed. The precipitate was removed by filtration using a PTFE filter, and the precursor solution (SnI 2 In the same manner, reducing agent 2 was added to SnI 2 Solutions were obtained in which 1.0 and 10.0 mol % of the compound was added. EXAMPLES
[0152] Fabrication of inverted tin-containing perovskite solar cells A patterned transparent conductive glass substrate (ITO, 25 mm × 25 mm, 5 Ω, Geomatec Co., Ltd. Japan) was ultrasonically cleaned with 1 w% neutral detergent solution, acetone, and 2-propanol, for 10 min each, and then UV ozone cleaned for 15 min.
[0153] After filtering the aqueous dispersion of PEDOT:PSS (Clevious P VP AI 4083) through a PTFE filter, about 400 μL was applied onto an ITO substrate and spin-coated (500 rpm with a slope of 1 s, spin-coated for 9 s, then 4000 rpm with a slope of 1 s, spin-coated for 60 s, and stopped with a slope of 1 s). The substrate was then heated at 140 °C to deposit a PEDOT:PSS layer (hole transport layer) with a thickness of about 20 nm. The resulting substrate was placed in a glove box for the subsequent deposition of the perovskite layer.
[0154] In the same manner as in the preparation of the perovskite precursor solution (1), the reducing agent 1 was replaced with SnI 2 Perovskite precursor solutions were obtained with 0.1, 0.5, 1.0, and 5.0 mol% of EDOT:PSS added. Approximately 200 μL of this solution was applied to a PEDOT:PSS substrate by spin coating, and chlorobenzene heated to 65 °C was added for 300 A brown film was obtained by dropping 1 μL of chlorobenzene onto the substrate (5000 rpm with a slope of 5 seconds, followed by 60 seconds of spin coating with chlorobenzene dropped between the last 2 and 1 seconds, and stopping at the slope of 1 second). The brown film was annealed at 45 °C for 10 minutes, 65 °C for 10 to 30 minutes, and then 100 °C for 5 minutes, followed by 100 °C for 30 minutes to produce a black perovskite layer. The resulting perovskite film was 60 (20 nm), BCP (8 nm), and Ag (100 nm) were deposited by vacuum deposition to fabricate an inverted-type perovskite solar cell element containing tin.
[0155] SEM observation of the perovskite film surface confirmed that the addition of reducing agent 1 did not affect the morphology of the perovskite crystals, and that a dense film with high surface coverage was obtained in either case (Figure 5). When the solar cell characteristics were evaluated under an inert gas atmosphere, the short-circuit current density (J sc (current density J at 0V voltage), open circuit voltage (V ocThe photoelectric conversion efficiency (PCE) was increased to a maximum of 7.05% by adding 0.5 mol% of reducing agent 1 (Figure 6, Table 1).
[0156] [Table 1] EXAMPLES
[0157] Fabrication of inverted tin-containing perovskite solar cells In the same manner as in the preparation of the perovskite precursor solution (2), the reducing agent 2 was replaced with SnI 2 Perovskite precursor solutions were obtained by adding 0.5, 1.0, 5.0, and 10.0 mol % of tin to the material. Using these solutions, in the same manner as in Example 2, inverted-type tin-containing perovskite solar cell elements were fabricated. SEM observation of the perovskite film surface confirmed that the morphology of the perovskite crystals did not change with the addition of reducing agent 2 or with different amounts of reducing agent 2, and that a dense film with high surface coverage was obtained in either case (Figure 7). When the solar cell characteristics were evaluated under an inert gas atmosphere, the addition of reducing agent 2 resulted in sc The PCE was improved by reducing agent 2 with SnI 2 Adding 1.0 mol% to the mixture gave a maximum of 8.45% (Figure 8, Table 2). sc The increase in is believed to be due to the suppression of carrier recombination in the perovskite layer.
[0158] [Table 2] EXAMPLES
[0159] Checking reproducibility In the same manner as in the preparation of the perovskite precursor solution (2), the reducing agent 2 was replaced with SnI 2A perovskite precursor solution with 1.0 mol% of tin added to the solution and a solution without the addition were prepared. Using these, 20 tin-containing perovskite solar cell elements of each inverted structure were fabricated in the same manner as in Example 2. The solar cell characteristics of these elements were evaluated under an inert gas atmosphere. As a result, the addition of reducing agent 2 reduced the J sc The increase in V oc , FF showed almost the same values. (Figs. 9, 10, and 11). As a result, it was found that the PCE improved from 6.9% to 7.5% on average (Fig. 12). EXAMPLES
[0160] Thickening of perovskite layer A tin-containing perovskite-type solar cell element having an inverted structure was produced in the same manner as in Example 2 using the perovskite precursor solution (3) prepared as described below. SEM observation of the perovskite film surface revealed that the grain size of the perovskite crystals increased from approximately 500 nm to approximately 1 μm by increasing the concentration of the precursor solution from 0.9 M to 1.2, 1.3, and 1.4 M. In addition, it was confirmed that the morphology of the perovskite crystals did not change with or without the addition of reducing agent 2, and that a dense film with a high surface coverage was obtained in all cases (Figure 13). In addition, cross-sectional SEM observation of the obtained element revealed that the film thickness of the perovskite layer increased from 210 nm (0.9 M) to 450 nm (1.4 M) by increasing the concentration of the precursor solution from 0.9 M to 1.2, 1.3, and 1.4 M (Figure 14). The solar cell characteristics of the obtained element were evaluated under an inert gas atmosphere. It was found that the addition of reducing agent 2 increased the solar cell performance regardless of the concentration of the precursor solution (1.2, 1.3, 1.4 M). sc The J value was improved (Fig. 15, Table 3). sc The amount of reducing agent 2 was increased, and SnI 2The device fabricated using a 1.4 M precursor solution containing 1.0 mol% of ZnO showed the highest PCE of 8.14% in this study. This result demonstrated that efficient charge recovery is possible even when a thick perovskite layer of about 450 nm is used due to the long carrier lifetime.
[0161] [Table 3]
[0162] The perovskite precursor solution (3) was obtained as follows.
[0163] Precursor solution (3): Perovskite precursor solution with added reducing agent 2 SnI in a glove box 2 (1341 mg, 3.6 mmol),FAI (464 mg, 2.7 mmol),MAI (143 mg, 0.9 mmol),SnF 2 (56 mg, 0.36 mmol) was dissolved in ultra-dehydrated DMSO (3.0 mL) at 45 °C. After stirring at 45 °C for 1 h, the mixture was filtered through a PTFE filter and FA was obtained. 0.75 MA 0.25 SnI 3 The precursor solution (1.2 M) was prepared in the same manner. 0.75 MA 0.25 SnI 3 Precursor solutions (1.3 M and 1.4 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (2) (9.9 mg, 0.035 mmol) was dissolved in DMF (50 μL) at 65 °C, and 1 mL of FA 0.75 MA 0.2 5 SnI 3 17 μL of this was added dropwise to the precursor solution (1.2 M). The addition of reducing agent 2 resulted in the formation of yellow FA. 0.75 MA 0.25 SnI 3The precursor solution changed to a dark green suspension. After stirring for 15 min at 45 °C, the suspension turned yellow again and a precipitate formed. The precipitate was removed by filtration using a PTFE filter, and the FA with 1.0 mol% of reducing agent 2 was 0.75 MA 0.25 SnI 3 A precursor solution (1.2 M) was obtained. Similarly, FA with 1.0 mol% of reducing agent 2 was 0.75 MA 0.25 SnI 3 Precursor solutions (1.3 M and 1.4 M) were obtained. EXAMPLES
[0164] Optimization of the method of adding reducing agent 2 In the glove box (1) SnI 2 (335 mg, 0.9 mmol),FAI (116 mg, 0.7 mmol),MAI (36 mg, 0.2 mmol),SnF 2 (14 mg, 0.09 mmol), (2) SnI 2 (335 mg, 0.9 mmol), (3) SnF 2 (14 mg, 0.09 mmol), (4) SnI 2 (335 mg, 0.9 mmol),FAI (116 mg, 0.7 mmol),MAI (36 mg, 0.2 mmol),SnF 2 (14 mg, 0.09 mmol) were dissolved in ultra-dehydrated DMSO (1.0 mL) at 45 °C, and (1) and (4) FA were 0.75 MA 0.25 SnI 3 DMSO solution of precursor (0.9 M), (2) SnI 2 DMSO solution (0.9 M), (3) SnF 2 A DMSO solution (0.09 M) was prepared.
[0165] 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (2) (9.9 mg, 0.035 mmol) was dissolved in DMF (50 μL) at 65 °C, and 13 μL of this solution was added dropwise to 1 mL of each of solutions (2), (3), and (4). 2 (14 mg, 0.09 mmol) was added to (3) 2 (335 mg, 0.9 mmol), FAI (116 mg, 0.7 mmol), and MAI (36 mg, 0.2 mmol) were added to the FA 0.75 MA 0.25 SnI 3 A precursor solution (0.9 M) was prepared. These solutions (1) to (4) were used to form a perovskite layer on a quartz substrate in the same manner as in Example 1.
[0166] SEM observation of the surface of the obtained perovskite film revealed that SnI 2 It was found that the grain size of the perovskite crystals increased to approximately 2 μm only when reducing agent 2 was added to the DMSO solution (Entry (2)) (Figure 16-2).
[0167] When PL measurements and time-resolved PL measurements were performed, it was found that the PL spectrum of only Entry (2) was shifted to shorter wavelengths by about 0.02 eV and the full width at half maximum was broadened to 104 meV (Figure 17). The reason for the shift to shorter wavelengths is presumably due to the increase in the grain size of the perovskite crystals, which reduced the proportion of the crystal surface area that is likely to become a recombination site. In addition, the emission lifetime was longer than that of SnI 2 and FAI + MAI + SnI 2 + SnF 2 When reducing agent 2 was added to the DMSO solution of (Entry (2) and (4)), the time was extended to 19.0 ns and 16.8 ns, respectively. However, the result of Entry (2) is considered to be largely due to the increase in the grain size of the perovskite crystals (Figure 18).
[0168] Thus, these precursor solutions (1), (2), and (4) were used to form a perovskite layer on a PEDOT:PSS substrate in the same manner as in Example 2. SEM observation of the surface of the obtained perovskite film revealed that perovskite crystals with a grain size of 1 μm or less were formed regardless of which precursor solution was used (Figure 19). The solar cell characteristics were evaluated for an inverted structure device fabricated in the same manner as in Example 2 using these films, and the results showed that FAI + MAI + SnI 2 + SnF 2 The best PCE (8.0%) was obtained when reducing agent 2 was added to the DMSO solution of (Entry (4)) (Figure 20, Table 4).
[0169] [Table 4] EXAMPLES
[0170] Optical properties of I-Br mixed perovskite films The Br was adjusted as described below. - A perovskite layer was formed on a quartz substrate in the same manner as in Example 1 using an I-Br mixed perovskite precursor solution (4) containing 0.0 to 25% of I—Br, and PL measurement and time-resolved PL measurement were performed. From the PL and time-resolved PL measurements, it was confirmed that the fluorescence lifetime of both I-Br mixed perovskite films was significantly extended by adding reducing agent 2 while maintaining the fluorescence wavelength, from about 2 ns to a maximum of 11 ns (Figures 21 and 22). 0.75 MA 0.25 SnI 3 This suggests that, as in the case of (1), the recombination of carriers generated by photoexcitation was suppressed while the structure and composition of the perovskite were maintained.
[0171] The perovskite precursor solution (4) was obtained as follows.
[0172] Precursor solution (4): I-Br mixed perovskite precursor solution SnI in a glove box 2 (335 mg, 0.9 mmol),FABr (84 mg, 0.7 mmol),MAI (36 mg, 0.2 mmol), SnF 2 (14 mg, 0.09 mmol) was dissolved in ultra-dehydrated DMSO (1.0 mL) at 45 °C. After stirring at 45 °C for 1 h, the solution was filtered through a PTFE filter and dissolved in FA containing 25% Br. 0.75 MA 0.25 Sn(I 0.75 Br 0.25 ) 3 The precursor solutions were prepared in the same manner. 0.75 MA 0.25 Sn(I 0.95 Br 0.05 ) 3 and F.A. 0.75 MA 0.25 Sn(I 0.80 Br 0.10 ) 3 A precursor solution was prepared by dissolving 2,3,5,6-tetramethyl-1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (2) (9.9 mg, 0.035 mmol) in DMF (50 μL) at 65 °C and adding 500 μL of FA 0.75 MA 0.25 Sn(I 1-x Br x ) 3 (x=0.0, 0.05, 0.10, 0.25) 6.5 μL was dropped into the precursor solution. By adding reducing agent 2, yellow FA 0.75 MA 0.25 Sn(I 1-x Br x ) 3 (x=0.0, 0.05, 0.10, 0.25) The precursor solution turned into a dark green suspension. After stirring for 15 min at 45°C, the suspension turned yellow again and a precipitate formed. The precipitate was removed by filtration using a PTFE filter, and the reducing agent 2 was replaced with SnI 2 FA added at 1.0 mol% (converted)0.75 MA 0.25 Sn(I 1-x Br x ) 3 (x=0.0, 0.05, 0.10, 0.25) precursor solutions were obtained. EXAMPLES
[0173] Regular structure tin-containing perovskite solar cells The patterned transparent conductive glass substrate (FTO, 25 mm × 25 mm, Asahi Glass Co., Ltd., Japan) was ultrasonically cleaned in 1 w% neutral detergent solution, acetone, 2-propanol, and distilled water, respectively, for 10 min each, and finally, UV ozone cleaning was performed for 15 min. Titanium di(isopropoxide)bis(acetylacetonate) (Ti(OiPr)) in 39 mL of ethanol (wako, ultra-dehydrated) 2 (acac) 2 The FTO substrates (transparent electrodes) were placed on a hot plate at 450 °C, and Ti(OiPr) 2 (acac) 2 Spray the solution (carrier gas: N 2 , 0.5 MPa), compact TiO 2 The resulting substrate was then coated with TiCl 4 The substrate was immersed in 100 mL of an aqueous solution of ZnO (440 μL, special grade, Wako Pure Chemical Industries Ltd., Japan) at 70 °C for 30 min. The substrate was then baked at 500 °C for 20 min to form a (hole) blocking layer.
[0174] The obtained compact TiO 2 On top of the hole blocking layer, a TiO 2Approximately 190 μL of an ethanol solution (paste:ethanol = 1:8 (mass ratio)) of paste (PST-18NR, JGC Catalysts and Chemicals Ltd.) was dropped and spin-coated to produce mesoporous TiO with a thickness of approximately 100–150 nm. 2 A layer (electron transport layer) was formed.
[0175] Mesoporous TiO immediately after UV ozone treatment 2 The substrate on which the layer (electron transport layer) had been prepared was placed in a glove box. Approximately 200 μL of the perovskite precursor solution (4) was applied onto the PEDOT:PSS substrate and spin-coated, during which 300 μL of chlorobenzene heated to 65 °C was dropped to obtain a brown film (5 seconds at 5000 rpm, 60 seconds of spin-coating were followed by dropping chlorobenzene between the last 2 and 1 seconds, and the slope was stopped at 1 second). The obtained brown film was annealed at 45 °C for 10 minutes, 65 °C for 10 to 30 minutes, and then 100 °C for 5 minutes, followed by annealing at 100 °C for 30 minutes to produce a black perovskite layer.
[0176] A hole transport material (PTAA; poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], 20.2 mg) and 4-isopropyl-4′-methyldiphenyliodonium tetrakis(pentafluorophenyl)borate (TPFB, 2.7 mg) were dissolved in 1 mL of chlorobenzene. After stirring for 30 min, the solution was filtered through a membrane filter, and the filtrate was spin-coated onto the perovskite layer. The resulting substrate was annealed at 70 °C for 5 min to form a hole transport layer, and then an 80 nm gold electrode was deposited on the hole transport layer by vacuum deposition to obtain a tin-containing perovskite solar cell with a normal structure.
[0177] When the solar cell characteristics were evaluated under an inert gas atmosphere, the addition of reducing agent 2 reduced the sc The PCE was improved by reducing agent 2 with SnI 2 FA added at 1.0 mol% (converted) 0.75 MA 0.25 Sn(I0. 95 Br 0.05 ) 3 The element fabricated using the precursor solution had the highest external quantum yield (EQE) of 2.9% in this study (Figure 23, Table 5). In addition, when the external quantum yield (EQE) of each element was measured, the reduction agent 2 was changed to SnI 2 FA added at 1.0 mol% (converted) 0.75 MA 0.25 Sn(I 1―x Br x ) 3 The IPCE of the elements fabricated using the precursor solutions (x=0.0, 0.05) was high, exceeding 80% (Figure 24).
[0178] [Table 5] EXAMPLES
[0179] 119 Sn NMR measurement In the glove box, (1) SnI 2 (88 mg, 0.24 mmol), (2) SnF 2 (88 mg, 0.56 mmol), (3) SnI 4 (88 mg, 0.14 mmol), (4) SnI 4 (88 mg, 0.14 mmol) and SnF 2 (22 mg, 0.14 mmol) in approximately 750 μL of DMSO-d 6 The mixture was dissolved in 119 Sn NMR measurements (224 MHz, Bruker Avance III 600US Plus NMR) were performed. Then, 1 equivalent of reducing agent 2 was added to each of them again in the glove box, 119 Sn NMR measurements were carried out.
[0180] First, regarding (1), SnI 2The peaks derived from SnI 2 On the other hand, in regard to (2), after the addition of reducing agent 2, the reactivity to SnF 2 Since the peak due to the reduction disappeared, it is considered that the divalent tin in the solution was reduced and precipitated as solid zero-valent tin. This is because the reducing agent 2, SnF 2 This suggests that the antibody has a high reactivity to β-lactamase (Figure 26).
[0181] Regarding this phenomenon, SnF 2 When reducing agent 2 was added to a DMSO solution (0.09 M) of the above, and the resulting suspension was observed under a transmission electron microscope, it was confirmed that nanoparticles with diameters of up to about 15 nm had been formed (Figure 27).
[0182] Next, regarding (3), after the addition of reducing agent 2, SnI 4 In addition to the peaks due to SnI 2 The peaks due to SnI were obtained by reducing agent 2. 4 It was confirmed that SnF was partially reduced (Fig. 28). 2 After adding reducing agent 2 in the presence of SnI, the peaks due to tetravalent tin completely disappeared, and the peaks due to SnI 2 Only the peaks due to SnF were obtained (Fig. 29). 2 Highly reactive zero-valent Sn nanoparticles and SnI 4 This suggests that tetravalent tin was effectively reduced by reacting with tin in the solution. EXAMPLES
[0183] Et 3 Effects of SiH addition on optical properties and solar cell characteristics The Et 3 SiH and SnI 2A perovskite layer was formed on a quartz substrate in the same manner as in Example 1 using the perovskite precursor solution (5) to which 0.0 to 10.0 mol % had been added, and time-resolved PL measurements were performed. As a result, Et 3 SiH and SnI 2 It was found that the fluorescence lifetime was extended from 5.9 ns to 8.0 ns by adding 1.0 mol% to Sn (Figure 30). 4+ Et 3 This is expected to be due to the decrease caused by the addition of SiH.
[0184] Next, a tin-containing perovskite solar cell element with an inverted structure was fabricated in the same manner as in Example 2 using the perovskite precursor solution (5). 3 It was found that the presence or absence of SiH addition and its amount did not affect the perovskite crystal morphology (Figure 31). When the solar cell characteristics were evaluated under an inert gas atmosphere, as expected from the results of time-resolved PL measurements, Et 3 By adding SiH, J sc increases, and Et 3 SiH and SnI 2 The PCE was maximized (5.31%) when 1.0 mol% of Zn was added to the perovskite layer (Figure 32). This result also suggests that the recombination of carriers generated in the perovskite layer was suppressed.
[0185] Precursor solution (5): Et 3 Perovskite precursor solution doped with SiH SnI in a glove box 2 (1341 mg, 3.6 mmol),FAI (464 mg, 2.7 mmol),MAI (143 mg, 0.9 mmol),SnF 2 (56 mg, 0.36 mmol) was dissolved in ultra-dehydrated DMSO (4.0 mL) at 45 °C. After stirring at 45 °C for 1 h, the mixture was filtered through a PTFE filter and the FA 0.75 MA 0.25 SnI 3The precursor solution was prepared by degassing and dehydrating Et 3 SiH in 1 mL of FA 0.75 MA 0.25 SnI 3 After stirring at 45 °C for 15 min, the precursor solution (SnI 2 1.0 mol% Et 3 In the same manner, Et 3 SiH and SnI 2 Solutions were obtained in which 5.0 and 10.0 mol % of the compound was added. EXAMPLES
[0186] Preparation of perovskite films using the scavenger method In a glove box (Ar gas, O 2 < 0.1 ppm, H 2 O < 0.1 ppm), SnI 2 (335.3 mg, 0.90 mmol) or SnI 2 (dmf) complex (401.0 mg, 0.90 mmol), FAI (116.1 mg, 0.68 mmol), MAI (35.8 mg, 0.23 mmol), and SnF 2 (14.1 mg, 0.09 mmol, 10 mol%) was dissolved in ultra-dehydrated DMSO (1.0 mL). The mixture was stirred at 45 °C for 30 min and then added 0.9 M FA. 0.75 MA 0.25 SnI 3A precursor solution was obtained. This solution was purified by the scavenger method. Specifically, a 0.9 M DMF solution (10 μL, 0.09 mmol, 1 mol%) of the reducing agent 1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (TM-DHP) was added dropwise to the precursor solution. The addition of the reducing agent TM-DHP caused the solution to change from a yellow solution to a yellow-gray suspension (Figure 33). After stirring for 15 minutes at 45 °C, the suspension became a yellow solution again, and a precipitate with a metallic luster was formed. After stirring for another 15 minutes, the precipitate was removed by filtration using a PTFE filter. Approximately 200 μL of this solution was applied to a PEDOT:PSS substrate and spin-coated, during which 300 μL of chlorobenzene heated to 65 °C was dropped to obtain a brown film (5 seconds ramp at 5000 rpm, 60 seconds spin-coated, chlorobenzene was dropped between the last 2 and 1 seconds, and the ramp was stopped at 1 second). The brown film obtained was annealed at 45 °C for 10 minutes, 65 °C for 10 to 30 minutes, and 100 °C for 10 minutes to produce a black perovskite layer.
[0187] Figure 33 is a photograph in lieu of a drawing showing the state of scavenger treatment. Figure 33 shows photographs of the precursor solution before (left), immediately after (middle), and after 15 minutes of stirring (right) of the reducing agent TM-DHP.
[0188] Surface and cross-sectional SEM observations were performed on perovskite thin films prepared using precursor solutions that were not scavenger-treated and precursor solutions that were scavenger-treated. SU8010 (Hitachi High-Technologies Co.) was used for SEM observations.
[0189] Figure 34 shows SEM images in lieu of drawings showing (a) the surface and (b) the cross section of a tin-containing perovskite thin film. Figure 34 shows that the morphology of the thin film hardly changes even when the scavenger treatment is performed, and a thin film with a thickness of about 190 nm and a high surface coverage can be obtained.
[0190] XPS analysis of Sn 4+ Quantification of Sn contained in perovskite thin films 4+ X-ray photoelectron spectroscopy (XPS) was performed to quantify the amount of the species. An ESCA-3400HSE (Shimadzu Co.) was used for the XPS measurements. To minimize the effect of air exposure during sample setting, a 20 nm thick BCP protective layer was evaporated onto the perovskite thin film to prepare the measurement sample.
[0191] Figure 35 shows a diagram for quantitative evaluation of tin ions contained in a perovskite thin film. Figure 35(a) shows a cross-sectional SEM image in place of a drawing, and Figure 35(b) shows the Sn 3d 5 / 2 The XPS spectrum is shown.
[0192] As shown in Fig. 35(a), when a cross-sectional SEM observation was performed on a sample from which only the protective layer had been removed by argon etching, the film thickness of the perovskite layer was approximately 190 nm. As shown in Fig. 35(b), the Sn 3d 5 / 2 From the spectrum, it was found that the Sn on the surface of the perovskite thin film was removed by the scavenger method. 4+ It was found that the amount of SiO2 had decreased from 6.6% to 4.7%. One or more 5 mm square measurement samples were then obtained from near the center of gravity (center of the surface) of the 2.5 cm square measurement sample, and XPS measurements were performed using the obtained 5 mm square measurement samples.
[0193] Next, the Sn inside the perovskite film 4+ To estimate the amount of Sn 3d, the thin films prepared using the scavenger method were argon etched for 4 or 8 seconds at an applied voltage of 0.5 V and an emission current of 20 mA. As shown in Fig. 35(a), the thicknesses of the perovskite layers in these samples were approximately 170 nm (depth 20 nm) and 150 nm (depth 40 nm), respectively. As shown in Fig. 35(b), the Sn 3d 5 / 2 From the spectrum, Sn inside the perovskite 4+The amount was found to be smaller than that at the surface, decreasing to 1.2% at a depth of 20 nm and to 0.0% at a depth of 40 nm.
[0194] Optical property measurement The perovskite film formed on a quartz substrate by the method described above was placed in a sample case filled with argon, and fluorescence (PL) measurements and time-resolved PL measurements were performed. A picosecond laser pulse (wavelength 688 nm, Advanced Laser Diode Systems Co., Ltd.) was used as the excitation light for the measurements. The excitation density at the sample position was 127 nJ / cm. 2 The measurements were performed under weak excitation conditions. PL spectra were measured using a spectrometer and a nitrogen-cooled CCD camera (Princeton Instruments). In the time-resolved PL measurements, PL from the sample was detected with an avalanche photodiode (IDQ Co., Ltd), and time-resolved decay curves were obtained using a time-correlated single-photon counting board (Becker and Hickl Co., Ltd).
[0195] Figure 36 is a graph instead of a drawing showing the results of measuring the optical properties of a tin-containing perovskite thin film. Figure 36(a) shows the fluorescence spectrum, and Figure 36(b) shows the time-resolved decay curve.
[0196] As shown in Figures 36(a) and 36(b), PL and time-resolved PL measurements revealed that when the scavenger method was used, the fluorescence intensity increased by about two times without changing the peak position, and the fluorescence lifetime was significantly extended from 4.0 ns to 14.3 ns. This result suggests that the recombination of carriers generated by photoexcitation was suppressed while the structure and composition of the perovskite were maintained.
[0197] 119 Sn NMR measurement SnBr 4 , SnCl 4 DMSO-d 6 Add 1 equivalent of the reducing agent TM-DHP to the solution, 119Sn NMR measurements (224 MHz, Bruker Avance III 600US Plus NMR) were performed, and the results are shown in Figure 37.
[0198] FIG. 37 is a diagram related to elucidation of the mechanism by scavengers. Figure 37(a) shows the change in the SnF 2 DMSO-d 6 27 is a graph, instead of a drawing, showing the results of NMR measurements indicating the presence of divalent tin and tetravalent tin in solution, and is the same as the graph in FIG. 26. Figure 37(b) shows the change in the SnI 2 DMSO-d 6 26 is a graph, instead of a drawing, showing the results of NMR measurements indicating the presence of divalent tin and tetravalent tin in solution, and is the same as the graph in FIG. 25. Figure 37(c) shows the change in the concentration of SnBr before (top) and after (bottom) the addition of TM-DHP. 2 DMSO-d 6 1 is a graph, instead of a drawing, showing the results of NMR measurements indicating the presence of divalent tin and tetravalent tin in solution. Figure 37(d) shows the change in the concentration of SnCl before (top) and after (bottom) the addition of TM-DHP. 2 DMSO-d 6 1 is a graph, instead of a drawing, showing the results of NMR measurements indicating the presence of divalent tin and tetravalent tin in solution. Figure 37(e) shows the results of the SnF 2 DMSO-d 6 1 is a photograph in lieu of a drawing showing a solution. Figure 37(f) shows the Sn formation after the addition of TM-DHP (right). 0 27 is a TEM photograph in place of a drawing showing nanoparticles, which is identical to the TEM photograph in FIG.
[0199] As shown in Fig. 37(a), SnF 2 When TM-DHP was added to a solution containing only SnF2 Regarding this phenomenon, the suspension obtained immediately after adding the reducing agent TM-DHP (Figure 37(e)) was observed by a transmission electron microscope (TEM), and it was found that nanoparticles with a particle size of 15 nm or less were formed, as shown in Figure 37(f).
[0200] As shown in Fig. 37(b), SnI 2 was not reduced by TM-DHP. 4 The reduction of SnF by TM-DHP was 2 Selective reduction of Sn 0 (ii) the formation of Sn nanoparticles; 0 SnI on the nanoparticle surface 4 Furthermore, as shown in Figure 37(c) and Figure 37(d), the reduction of SnBr 2 or SnCl 2 was not reduced by TM-DHP, and SnF 2 Selectivity for was confirmed.
[0201] Therefore, it can be said that the tin-containing perovskite layer preferably contains not only I but also F. The atomic ratio I / F of I to F may be 0.1 or more and 10 or less, 0.2 or more and 8 or less, 0.3 or more and 7 or less, 0.5 or more and 4 or less, or 0.5 or more and 2 or less.
[0202] Fabrication of Perovskite Solar Cells A patterned transparent conductive glass substrate (ITO, 25 mm × 25 mm, 10 Ω, Geomatec Co., Ltd. Japan) was ultrasonically cleaned in the following order: water, acetone, cleaning solution (Semicoclean 56, Furuuchi Chemical), water, and 2-propanol for 15 minutes each, and then plasma treatment was performed. After filtering the aqueous dispersion of (Clevious P VP AI 4083) through a PVDF filter, about 400 μL was applied onto an ITO substrate and spin-coated (500 rpm with a slope of 1 s, spin-coated for 9 s, then 4000 rpm with a slope of 1 s, spin-coated for 60 s, and stopped with a slope of 1 s). The substrate was then heated at 140 °C for 20 min in a glove box and another 20 min at 140 °C to form a PEDOT:PSS layer (hole transport layer) with a thickness of about 20 nm. A perovskite layer was formed on the PEDOT:PSS layer by the method described above. C60 (20 nm) (electron transport layer), BCP (8 nm) was laminated by vacuum deposition, and finally, Ag (100 nm) was deposited by vacuum deposition as a metal electrode. The solar cell characteristics were evaluated under an inert gas atmosphere. The results are shown in Figure 38 and Table 6.
[0203] Figure 38 is a graph instead of a drawing showing the characteristics of a perovskite solar cell. Figure 38(a) shows a current density-voltage curve, and Figure 38(b) shows the distribution of photoelectric conversion efficiency (PCE) of 40 cells.
[0204] [Table 6]
[0205] From Figure 38 and Table 6, it can be seen that the average photovoltaic conversion efficiency (PCE) is improved from 6.6% to 8.9% by using the scavenger method. As shown in Table 6, the short circuit current density (J SC ) as well as the open circuit voltage (V OC ) and fill factor (FF), it can be seen that the recombination of carriers is effectively suppressed. As shown in Figure 38(a), the champion cell using the scavenger method has a conversion efficiency of 9.9% (J = 21.1 mA cm -2 , VOC = 0.63 V, FF = 0.74) was obtained. In addition, as shown in Figure 38(b), it was confirmed that high reproducibility was obtained from the histogram of the conversion efficiency of 40 cells.
[0206] Improving photoelectric conversion efficiency through surface treatment The open circuit voltage (VOC) of the tin-containing perovskite element was a maximum of 0.63 V even when using the scavenger method, and the FA 0.75 MA 0.25 SnI 3 Considering the band gap (1.36 eV), it can be said that this is still insufficient. We thought that the large voltage loss (0.73 V) was due to the interface between the perovskite layer and the charge transport layer. Therefore, in addition to the scavenger method, we first treated the perovskite surface with ethylenediamine (EDA) and measured various physical properties. The results are shown in Figure 39 and Table 7.
[0207] Figure 39 shows the physical properties of the surface-treated perovskite layer. Figure 39(a) is a graph replacing a drawing showing the current density-voltage curve of a tin-containing perovskite solar cell. Figure 39(b) is a diagram showing an energy level diagram. Figure 39(c) is a graph replacing a drawing showing the external quantum efficiency (EQE) and internal quantum efficiency (IQE). Figure 39(d) is a graph replacing a drawing showing the distribution of photoelectric conversion efficiency (PCE) of 30 cells.
[0208] [Table 7]
[0209] As shown in Figure 39(a) and Table 7, the VOC increased to 0.68 V by the surface treatment. Furthermore, referring to Figure 39(b), in order to improve the connection of the energy levels of the perovskite layer and the electron transport layer (C60) and to suppress charge recombination at the interface, a thin PC 61 A layer of BM (<5 nm) was inserted. As shown in Fig. 39(c), this improved the conversion efficiency up to 11.5% (J = 22.0 mA cm -2 , VOC = 0.76 V, FF = 0.69). The integrated JSC calculated from the external quantum efficiency (EQE) spectrum was 21.6 mA cm -2The results showed good agreement with the values in the JV curves. Furthermore, as shown in Fig. 39(d), the histogram of the conversion efficiency of 30 cells confirmed that the average PCE was 10.2 ± 0.8%, which is highly reproducible.
[0210] This shows that a preferable solar cell or organic EL device can be obtained by cleaning the surface of the perovskite layer, which is the interface between the perovskite layer and the electron transport layer, with an amine solvent such as ethylenediamine. Therefore, this specification also provides a method for manufacturing a solar cell or organic EL device, which includes a step of treating the surface of the perovskite layer with a solvent (e.g., cleaning treatment), and then forming a layer (e.g., an electron transport layer) on the surface of the treated perovskite layer.
[0211] [Table 8] EXAMPLES
[0212] ASnI 3-X Br X Effect of scavenger methods on the system [MASnI using the scavenger method] 3-X Br X Preparation of perovskite films (X = 1.5, 3)] In a glove box (Ar gas, O 2 < 0.1 ppm, H 2 O < 0.1 ppm), SnI 2 (372.5 mg, 1.0 mmol), MAI (159.0 mg, 1.0 mmol), SnF 2 (14.1 mg, 0.10 mmol, 10 mol%) was dissolved in ultra-dehydrated DMSO (1.0 mL). The mixture was stirred at 45 °C for 30 min to give 1.0 M MASnI 3 The precursor solution was obtained. 2 (278.5 mg, 1.0 mmol) or SnBr 2(dmf) complex (351.6 mg, 1.0 mmol), MABr (112.0 mg, 1.0 mmol), SnF 2 (14.1 mg, 0.10 mmol, 10 mol%) was dissolved in ultra-dehydrated DMSO (1.0 mL). The mixture was stirred at 45 °C for 30 min to give 1.0 M MASnBr 3 A precursor solution was obtained. The resulting 1.0 M MASnI 3 Precursor solution and 1.0 M MASnBr 3 Mix 500 μL of the precursor solution into 1.0 M MASnI 1.5 Br 1 .5 The precursor solution was prepared.
[0213] Above 1.0 M MASnI 1.5 Br 1.5 Solution and 1.0 M MASnBr 3 A 1.0 M DMF solution (10 μL, 0.10 mmol, 1 mol%) of the reducing agent 1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (TM-DHP) was added to 1.0 mL of the solution, and the mixture was stirred at 45 °C for 30 min and then filtered using a PTFE filter. Approximately 200 μL of this solution was applied to a quartz substrate and spin-coated. During this process, 300 μL of chlorobenzene heated to 65 °C was dropped to obtain a brown film (slope was set to 5000 rpm for 5 s, and chlorobenzene was dropped between the last 2 and 1 s of the 60 s spin-coating, and the slope was stopped at 1 s). The obtained brown film was then incubated at 45 °C for 10 min, 65 °C for 10 to 30 min, and 100 °C for 10 to 30 min. The film was annealed at ℃ for 10 min to produce a brown perovskite layer.
[0214] [MASnI 3-X Br X Fluorescence properties of perovskite films (X = 1.5, 3) The perovskite film formed on the quartz substrate by the above method was placed in a sample case filled with argon, and fluorescence (PL) measurements and time-resolved PL measurements were performed. A picosecond laser pulse (wavelength 406 nm, Advanced Laser Diode Systems Co., Ltd.) was used as the excitation light for the measurements. The excitation density at the sample position was MASnI 1.5 Br 1.5 782 nJ / cm 2 , MASnBr 3 At 10 μJ / cm 2 The PL spectra were recorded using a spectrometer and a nitrogen-cooled CCD camera (Princeton For time-resolved PL measurements, the PL from the sample was detected with an avalanche photodiode (IDQ Co., Ltd), and time-resolved decay curves were obtained using a time-correlated single-photon counting board (Becker & Hickl Co., Ltd).
[0215] MASnI 1.5 Br 1.5 From PL and time-resolved PL measurements of the perovskite film, it was found that when the scavenger method was used, the peak position remained unchanged, the fluorescence intensity increased by about 10 times, and the fluorescence lifetime was significantly extended from 0.78 ns to 2.28 ns (Figure 40). This result suggests that the recombination of carriers generated by photoexcitation was suppressed while the structure and composition of the perovskite were maintained. 3 For the perovskite film, the fluorescence lifetime was shorter than the detection limit, but it was found that the fluorescence intensity increased by about three times by using the scavenger method (Figure 42).
[0216] [Sn by XPS 4+ Quantitative determination of Sn contained in perovskite thin films 4+X-ray photoelectron spectroscopy (XPS) was performed to quantify the amount of the species. A JPS-9010 (JEOL) was used for the XPS measurements. The samples were set in an argon-filled transfer vessel, so that the measurements were performed without exposing the samples to air.
[0217] MASnI 1.5 Br 1.5 Perovskite thin films, Sn 3d 5 / 2 From the spectrum, Sn 4+ The amount of Sn on the surface of the perovskite film was estimated by using the scavenger method. 4+ It was found that the amount of Sn in the thin film produced by the scavenger method decreased from 2.4% to 0.4% (Figure 42). Furthermore, argon etching was performed on the thin film produced by the scavenger method to remove Sn from the inside of the film. 4+ The amount of Sn is estimated at a depth of 40 nm. 4+ The amount was found to be 0.0% (Figure 42).
[0218] [Fabrication of perovskite solar cells] A patterned transparent conductive glass substrate (ITO, 25 mm × 25 mm, 10 Ω, Geomatec Co., Ltd. Japan) was ultrasonically cleaned in water, acetone, cleaning solution (Semicoclean 56, Furuuchi Chemical), water, and 2-propanol for 15 min each, and then plasma treated. After filtering an aqueous dispersion of PEDOT:PSS (Clevious P VP AI 4083) through a PVDF filter, approximately 300 μL was applied onto the ITO substrate and spin-coated (500 rpm with a slope of 1 s, spin-coated for 9 s, then 4000 rpm with a slope of 1 s, spin-coated for 60 s, and stopped with a slope of 1 s). The substrate was then heated at 140 °C for 20 min in a glove box and another 20 min at 140 °C to form a PEDOT:PSS layer (hole transport layer) with a thickness of approximately 20 nm.
[0219] In a glove box (Ar gas, O 2 < 0.1 ppm, H 2 O < 0.1 ppm), SnI2 (232.8 mg, 0.625 mmol), SnBr 2 (dmf) complex (131.9 mg, 0.375 mmol), FAI (129.0 mg, 0.75 mmol), MAI (40.0 mg, 0.25 mmol), SnF 2 (15.8 mg, 0.10 mmol, 10 mol%) in ultra-dehydrated DMSO (971 The mixture was stirred at 45 °C for 30 min and then dissolved in 1.0 M FA. 0.75 MA 0.25 SnI 2.25 Br 0.75 The precursor solution was obtained. Similarly, SnI 2 (232.8 mg, 0.625 mmol), SnBr 2 (dmf) complex (131.9 mg, 0.375 mmol), FAI (86.0 mg, 0.50 mmol), MAI (79.5 mg, 0.50 mmol), SnF 2 (15.8 mg, 0.10 mmol, 10 mol%) was dissolved in ultra-dehydrated DMSO (971 μL) and diluted with 1.0 M FA. 0.50 MA 0.50 SnI 2.25 Br 0.75 The precursor solutions were then subjected to a scavenger treatment using TM-DHP, and a perovskite layer was formed on the PEDOT:PSS layer by the method described above. 60 (20 nm) (electron transport layer), BCP (8 nm) were deposited by vacuum deposition, and finally, Ag (100 nm) was deposited by vacuum deposition.
[0220] When the solar cell characteristics were evaluated under an inert gas atmosphere, FA 0.75 MA 0.25 SnI 2.25 Br 0.75 The perovskite-based solar cell achieved a conversion efficiency of 7.4% (J SC = 17.1 mA cm -2 , V OC = 0.61 V, FF = 0.71), F.A. 0.50 MA 0.50 SnI 2.25 Br 0.75 The conversion efficiency (J SC = 16.9 mA cm -2 , V OC = 0.58 V, FF = 0.74) were obtained (Figure 43, Table 8). EXAMPLES
[0221] 2. Effect of scavenger method on Pb-Sn mixed perovskite [Cs using the scavenger method] 0.1 FA 0.6 MA 0.3 Pb 0.5 Sn 0.5 I 3 Preparation of perovskite films In a glove box (Ar gas, O 2 < 0.1 ppm, H 2 O < 0.1 ppm), SnI 2 (335.3 mg, 0.90 mmol), PbI 2 (414.9 mg, 0.90 mmol),CsI (46.6 mg, 0.18 mmol),FAI (185.8 mg, 1.08 mmol),MAI (85.8 mg, 0.54 mmol),SnF 2 (14.1 mg, 0.09 mmol, 10 mol% compared to SnI 2 ),Pb(SCN) 2 (5.8 mg, 0.018 mmol, 2 mol% compared to PbI 2 ) in ultra-dehydrated DMSO (250 μL) and DMF (750 μL). The mixture was stirred at 45 °C for 30 min and then cooled to 1.8 M Cs 0.1 FA 0.6 MA 0.3 Pb 0.5 Sn 0.5 I 3A precursor solution was obtained. A 1.0 M DMF solution of the reducing agent 1,4-bis(trimethylsilyl)-1,4-dihydropyrazine (TM-DHP) (9 μL, 0.09 mmol, 1 mol% compared to SnI 2 ) was added dropwise. After stirring at 45 °C for 30 minutes, the precipitate was removed by filtration using a PTFE filter. Approximately 200 μL of this solution was applied to a quartz substrate and spin-coated. During this process, 400 μL of chlorobenzene was added dropwise to obtain a brown film (slope was set to 1000 rpm for 5 seconds, and after 10 seconds, slope was set to 4000 rpm for 3 seconds, followed by another 40 seconds of spin-coating. 20 seconds after the 4000 rpm step began, chlorobenzene was added dropwise for 1 second). The obtained brown film was annealed at 100 °C for 10 minutes, and then stored at 65 °C until spin-coating of all substrates was completed, producing a black perovskite layer.
[0222] [Cs 0.1 FA 0.6 MA 0.3 Pb 0.5 Sn 0.5 I 3 Fluorescence properties of perovskite films] The perovskite film formed on the quartz substrate by the above method was placed in a sample case filled with argon, and fluorescence (PL) measurements and time-resolved PL measurements were performed. A picosecond laser pulse (wavelength 688 nm, Advanced Laser Diode Systems Co., Ltd.) was used as the excitation light for the measurements. The excitation density at the sample position was 127 nJ / cm. 2 The measurements were performed under weak excitation conditions. PL spectra were measured using a spectrometer and a nitrogen-cooled CCD camera (Princeton Instruments). In the time-resolved PL measurements, PL from the sample was detected with an avalanche photodiode (IDQ Co., Ltd.), and time-resolved decay curves were obtained using a time-correlated single-photon counting board (Becker & Hickl Co., Ltd.). PL measurements and time-resolved PL measurements showed that when the scavenger method was used, the peak position remained unchanged, but the fluorescence intensity increased by about three times, and the fluorescence lifetime was significantly extended from 1.17 μs to 1.68 μs (Figure 44). This result suggests that the recombination of carriers generated by photoexcitation was suppressed while the structure and composition of the perovskite were maintained.
[0223] [Fabrication of perovskite solar cells] Using the same device structure as the above-mentioned tin-containing perovskite solar cell, a Pb-Sn mixed perovskite solar cell was fabricated. The solar cell characteristics were evaluated under an inert gas atmosphere, and a conversion efficiency (J SC = 31.6 mA cm -2 , V OC = 0.80 V, FF = 0.79) was obtained (Figure 45).
[0224] [Sn by XPS 4+ Quantitative determination of Cs produced using the scavenger method 0.1 FA 0.6 MA 0.3 Pb 0.5 Sn 0.5 I 3 Perovskite thin films, Sn 3d 5 / 2 From the spectrum, Sn 4+ The ratio of Sn on the film surface is estimated as 4+ The ratio of Sn in the film was found to be 3.0%. 4+ The ratio of Sn at a depth of 40 nm is estimated. 4+ It was found that the proportion of [Industrial Applicability]
[0225] The present invention relates to a method for producing a perovskite layer, and can therefore be used in industries for producing solar cells and organic EL elements.
Claims
1. A method for manufacturing a semiconductor device comprising the steps of: Sn is the percentage of the tetravalent tin atomic content in the total of the tetravalent tin atomic content and the divalent tin atomic content in a region 40 nm deep from the center of the surface of the tin-containing perovskite layer. +4 40nm The value is 0% or more and 0.5% or less, Sn +4 40nm value, the percentage of the tetravalent tin atomic content in the total of the tetravalent tin atomic content and the divalent tin atomic content at the surface center of the tin-containing perovskite layer, Sn +4 表面 The ratio of values is 3 or more, The tin-containing perovskite layer has an average particle size of the tin-containing perovskite compound of 150 nm or more and 500 nm or less, The tin-containing perovskite layer comprises a compound represented by formula (Ia), (In formula (Ia), R 1 to R 4 may be the same or different and each is a hydrogen atom, a methyl group, or an ethyl group, and R 5 to R 10 may be the same or different and each is a methyl group or an ethyl group.) containing one or more selected from zero-valent tin, a pyrazine-based compound, a silicon-based compound including a compound represented by formula (Ia), and a germanium-based compound in a total amount of 0.01 ppm or more and 1000 ppm or less, Solar cell.
2. Sn is the percentage of the tetravalent tin atomic content in the total of the tetravalent tin atomic content and the divalent tin atomic content in a region 20 nm deep from the center of the surface of the tin-containing perovskite layer. +4 20nm The value is 0.1% or more and 5% or less, The ratio of the Sn +4 surface value to the Sn +4 20nm value is 3 or more and 20 or less, The solar cell according to claim 1 .
3. 2. The solar cell according to claim 1, wherein the atomic content of lead atoms relative to the content of tin atoms is 0% or more and 900% or less.
Citation Information
Patent Citations
Photoelectronic element
JP2015535390A
Lead-free solid-state organic-inorganic halide perovskite photovoltaic cells
US20150295194A1
Planar mixed-metal perovskites for optoelectronic applications
US20170053746A1
Tin (II) halide-based perovskite film, method for manufacturing same, and electronic device and photovoltaic device using same
WO2016121700A1